Microtubulin-SRC double-target inhibitor in crystal form, preparation method and application thereof

By preparing and optimizing the crystal form of tubulin-SRC dual-target inhibitor, the existing drugs have limited effect and drug resistance in the treatment of actinic keratosis, achieving significant inhibitory effect and good drug properties .

CN119306728APending Publication Date: 2025-01-14WUHAN HUMANWELL INNOVATIVE DRUG RES & DEV CENT LTD CO +1

Patent Information

Application Number
CN202410934361.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-14
Filing Date
2024-07-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing tubulin-SRC dual-target inhibitors have limited effectiveness in the treatment of actinic keratosis, and there are drug resistance and dose-limiting toxicity problems. It is necessary to develop new micro-microsine with better drug properties and stability. Tubulin-SRC dual-target inhibitor.

Method used

The free crystal form of tubulin-SRC dual-target inhibitor in crystal form and its preparation method are provided. The free crystal form and salt of the compound were determined by analysis of X-ray powder diffraction patterns and differential scanning calorimetry of Cu-Kα radiation. , optimized its stability and drug properties.

Benefits of technology

It has achieved significant inhibition of tubulin monomer polymerization and Src kinase activity, improved the effect of the treatment of actinic keratosis, and has good pharmacokinetic properties of local skin administration and low side effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306728A_ABST
    Figure CN119306728A_ABST
Patent Text Reader

Abstract

The invention provides a tubulin-SRC double-target inhibitor in a crystal form as well as a preparation method and application thereof, and particularly discloses 13 crystal forms of two free crystal forms and 10 salts of a compound as shown in a formula I as well as a preparation method and application thereof. The compound, the salt form and the crystal form can be used as a tubulin and Src kinase double-target inhibitor, and can also be used as a single tubulin or Src kinase inhibitor; the compound, the salt form and the crystal form can also obviously inhibit polymerization of tubulin monomers and inhibit cell proliferation; the compound has good pharmacokinetic properties of skin local administration and good druggability, can be used for preparing skin external preparations, and has the advantages of fast metabolism and small side effects. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a microtubule protein-SRC dual-target inhibitor in a crystal form, a preparation method and use thereof. Background Art

[0002] Microtubules are an important component of the cytoskeleton in eukaryotic cells and play an important role in maintaining cell morphology, signal transduction, organelle transport, cell motility, cell division and mitosis, and other cellular functions.

[0003] Microtubules are composed of two types of tubulin subunits, namely α-tubulin and β-tubulin. α-tubulin and β-tubulin form tubulin heterodimers, which are the basic units of microtubule assembly. Microtubule-targeting agents (MTAs) can destroy the dynamic stability and structure of microtubules, interfere with the formation of mitotic spindles, induce cell cycle arrest at the G2 / M phase, and promote cell apoptosis.

[0004] Microtubules are involved in many important cellular processes and have become one of the most important drug targets for the treatment of hyperproliferative diseases. Several microtubule-targeting agents approved by the US FDA, such as vinblastine and taxane compounds, are widely used to treat multiple solid tumors and hematological malignancies, but the drug resistance and dose-limiting toxicity of microtubule-targeting drugs limit their clinical efficacy. Compared with single-target drugs, dual-target inhibitors overcome drug resistance and can improve treatment effects, and have become a research hotspot, such as tubulin-SRC dual-target inhibitors, tubulin-receptor tyrosine kinases inhibitor (RTK) dual-target inhibitors, and tubulin-histone deacetylases inhibitor (HDAC) dual-target inhibitors.

[0005] Actinic keratosis (AK) is a skin disease associated with prolonged exposure to ultraviolet light. AK is the second most common disease among dermatologists in the United States. It is characterized by the uncontrolled proliferation of mutated keratinocytes, which is considered a precancerous lesion. If not treated in time, 20% of cases may develop into squamous cell carcinoma (SCC) of the skin. Currently, the tubulin-SRC dual-target inhibitor Tirbanibulin has a significant effect in the local treatment of AK in clinical practice (NCT03285477) and has been approved by the FDA for marketing, which suggests that the development of new tubulin-SRC dual-target inhibitors with better effects for the local treatment of AK may be a potential direction.

[0006] The Chinese invention patent application with application number 202211139978.7 describes compound I-2 (the compound shown in formula I of the present application) having tubulin-SRC dual-target inhibitory effect:

[0007]

[0008] On the basis of the good biological activity of the compound, it is necessary to develop a suitable salt form and its solid form to obtain improved drugability or other properties. Summary of the invention

[0009] The object of the present invention is to provide a tubulin-SRC dual-target inhibitor in crystalline form, a preparation method and use thereof. The dual-target inhibitor has a crystal form or a salt form as described in the present invention, and has advantages such as better stability. The crystal form or the salt form can be used as a tubulin and SRC kinase dual-target inhibitor, and can also be used as a single tubulin or SRC kinase inhibitor.

[0010] The present invention provides a free crystalline form A of a compound as shown in formula I,

[0011]

[0012] The free crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 14.49±0.2°, 17.02±0.2°, 18.42±0.2°, and 20.53±0.2°.

[0013] In one embodiment, the free crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following locations: 7.25±0.2°, 9.20±0.2°, 12.39±0.2°, and 13.77±0.2°.

[0014] In one embodiment, the free crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 3.66±0.2°, 7.25±0.2°, 9.20±0.2°, 11.13±0.2°, 12.39±0.2°, 13.77±0.2°, and 14.49±0.2°.

[0015] In one embodiment, the free crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 7.25±0.2°, 9.20±0.2°, 12.39±0.2°, 13.77±0.2°, 14.49±0.2°, 17.02±0.2°, 17.78±0.2°, 18.42±0.2°, and 20.53±0.2°.

[0016] In one embodiment, the free crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 3.66±0.2°, 7.25±0.2°, 9.20±0.2°, 11.13±0.2°, 12.39±0.2°, 13.77±0.2°, 14.49±0.2°, 17.02±0.2°, 17.78±0.2°, 18.42±0.2°, and 20.53±0.2°.

[0017] In one embodiment, the free crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 3.66±0.2°, 7.25±0.2°, 9.20±0.2°, 11.13±0.2°, 12.39±0.2°, 13.77±0.2°, 14.49±0.2°, 17.02±0.2°, 17.78±0.2°, 18.42±0.2°, 20.53±0.2°, and 20.92±0.2°.

[0018] In one embodiment, the free crystalline form A is an anhydrous crystalline form.

[0019] In one embodiment, the free crystalline form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 1:

[0020] Table 1

[0021]

[0022]

[0023] In one embodiment, the free crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Figure 1 shown.

[0024] In one embodiment, the free-state crystalline form A has a differential scanning calorimetry analysis chart with an endothermic peak starting point at 94.7±3°C.

[0025] In one embodiment, the free-state crystalline form A has an endothermic peak at 96.6±3°C in its differential scanning calorimetry analysis diagram.

[0026] In one embodiment, the free crystalline form A has a weight loss of about 0.98% at 150° C. in a thermogravimetric analysis diagram.

[0027] In one embodiment, the free form A has a differential scanning calorimetry analysis diagram substantially as follows: Figure 3 shown.

[0028] In one embodiment, the thermogravimetric analysis diagram of the free crystalline form A is substantially as follows: Figure 2 shown.

[0029] The present invention also provides a free crystalline form B of the compound shown in formula I,

[0030]

[0031] The free crystalline form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 16.55±0.2°, 17.77±0.2°, 20.36±0.2°, 21.24±0.2°, and 22.66±0.2°.

[0032] In one embodiment, the free crystalline form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following locations: 8.89±0.2°, 10.99±0.2°, 13.81±0.2°, 16.10±0.2°, and 19.65±0.2°.

[0033] In one embodiment, the free crystalline form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 8.89±0.2°, 10.99±0.2°, 13.81±0.2°, 16.10±0.2°, 16.55±0.2°, 17.77±0.2°, 19.65±0.2°, 20.36±0.2°, 21.24±0.2°, and 22.66±0.2°.

[0034] In one embodiment, the free crystalline form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 8.89±0.2°, 10.99±0.2°, 13.81±0.2°, 14.97±0.2°, 16.10±0.2°, 16.55±0.2°, 17.77±0.2°, 19.65±0.2°, 20.36±0.2°, 21.24±0.2°, 22.66±0.2°, 23.92±0.2°, 24.80±0.2°, 25.41±0.2°, and 26.65±0.2°.

[0035] In one embodiment, the free crystalline form B is an anhydrous crystalline form.

[0036] In one embodiment, the free state crystalline form B uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 2:

[0037] Table 2

[0038] Position [°2θ] Relative strength [%] Position [°2θ] Relative strength [%] 7.4873 3.10 22.6576 61.87 8.8864 9.12 23.9201 7.02 10.9912 18.04 24.7970 12.05 13.8121 14.37 25.4143 15.92 14.9693 6.34 26.6488 16.69 16.1011 36.37 27.7637 6.02 16.5486 39.23 28.3501 3.63 16.9933 5.23 29.5259 2.44 17.7740 100.00 30.7717 5.46 18.6972 5.30 31.9792 2.29 19.6520 31.67 33.3167 3.42 20.3614 65.65 37.7157 3.02 21.2371 58.26 39.0657 1.38 22.0673 19.39

[0039] In one embodiment, the free crystalline form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Figure 4 shown.

[0040] In one embodiment, the differential scanning calorimetry analysis diagram of the free-state crystalline form B shows an endothermic peak starting point at 77.2±3°C.

[0041] In one embodiment, the free-state crystalline form B has an endothermic peak at 84.5±3°C in its differential scanning calorimetry analysis chart.

[0042] In one embodiment, the free-state crystalline form B has an endothermic peak at 92.4±3°C in its differential scanning calorimetry analysis diagram.

[0043] In one embodiment, the free crystalline form B has a weight loss of about 0.48% at 150° C. in a thermogravimetric analysis diagram.

[0044] In one embodiment, the free-state crystalline form B has a differential scanning calorimetry analysis diagram substantially as follows: Figure 6 shown.

[0045] In one embodiment, the thermogravimetric analysis diagram of the free form B is substantially as follows: Figure 5 shown.

[0046] The present invention also provides a method for preparing a free-state crystalline form A of a compound as shown in formula I, wherein the compound as shown in formula I is dissolved in a solvent and volatilized at room temperature to obtain the free-state crystalline form A, wherein the solvent is an organic solvent or a mixed solvent, wherein the organic solvent includes but is not limited to: CHCl3, THF, acetone, toluene, cyclopentyl methyl ether, 2-methyltetrahydrofuran, isopropanol, IPAc, 2-butanone; and the mixed solvent is a mixed solvent of an organic solvent and water, wherein the mixed solvent includes but is not limited to: a mixed solvent of MeOH and H2O, and a mixed solvent of acetonitrile and H2O.

[0047] The present invention also provides a method for preparing the free crystalline form B of the compound as shown in formula I, which comprises concentrating the compound solution as shown in formula I under reduced pressure and drying at 40-60° C. to obtain the free crystalline form B; the solution is an alcohol solution or a halogenated hydrocarbon solution.

[0048] Preferably, the compound represented by formula I is dissolved in MeOH or dichloromethane and then rotary evaporated under reduced pressure, and the obtained colloidal sample is transferred to 50° C. and dried under vacuum to obtain the obtained product.

[0049] The present invention also provides a phosphate of the compound shown in formula I.

[0050] In a certain embodiment, the phosphate of the compound as shown in formula I is the phosphate crystal form A of the compound as shown in formula I, and in the phosphate crystal form A, the phosphate crystal form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and has diffraction peaks at 6.74±0.2°, 13.47±0.2°, 15.69±0.2°, 16.86±0.2°, and 18.09±0.2°.

[0051] In one embodiment, the phosphate crystal form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 6.74±0.2°, 13.47±0.2°, 15.69±0.2°, 18.09±0.2°, and 20.26±0.2°.

[0052] In one embodiment, the phosphate crystal form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and also has diffraction peaks at one or more of the following locations: 11.87±0.2°, 12.56±0.2°, 13.75±0.2°, 18.60±0.2°, 20.26±0.2°, and 25.26±0.2°.

[0053] In one embodiment, the phosphate crystal form A uses Cu-Kα radiation and has an X-ray powder diffraction pattern expressed in 2θ angles, with diffraction peaks at 6.74±0.2°, 11.87±0.2°, 12.56±0.2°, 13.47±0.2°, 13.75±0.2°, 15.69±0.2°, 16.86±0.2°, 18.09±0.2°, and 20.26±0.2°.

[0054] In one embodiment, the phosphate crystal form A uses Cu-Kα radiation and has an X-ray powder diffraction pattern expressed in 2θ angles, and has diffraction peaks at 3.40±0.2°, 6.74±0.2°, 7.47±0.2°, 11.87±0.2°, 12.56±0.2°, 13.47±0.2°, 13.75±0.2°, 14.94±0.2°, 15.69±0.2°, 16.86±0.2°, 18.09±0.2°, 18.61±0.2°, 20.26±0.2°, and 25.26±0.2°.

[0055] In one embodiment, the phosphate crystal form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 3:

[0056] Table 3

[0057]

[0058]

[0059] In one embodiment, the phosphate crystal form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Figure 7 shown.

[0060] In one embodiment, in the phosphate crystal form A, the molar ratio of the compound shown in formula I to phosphoric acid is 1:1.

[0061] In one embodiment, the differential scanning calorimetry analysis diagram of the phosphate crystal form A shows an endothermic peak starting point at 172.8±3°C.

[0062] In one embodiment, the phosphate crystal form A has an endothermic peak at 174.5±3°C in its differential scanning calorimetry analysis diagram.

[0063] In one embodiment, the phosphate crystal form A has a weight loss of about 4.40% at 150° C. in its thermogravimetric analysis diagram.

[0064] In one embodiment, the differential scanning calorimetry analysis diagram of the phosphate crystal form A is substantially as follows: Fig. 9 shown.

[0065] In one embodiment, the phosphate crystal form A has a thermogravimetric analysis diagram substantially as follows: Figure 8 shown.

[0066] The present invention also provides a method for preparing the phosphate crystal form A of the compound shown in formula I, comprising mixing the compound shown in formula I, phosphoric acid, and a solvent, and slurrying at room temperature to obtain the phosphate crystal form A of the compound shown in formula I;

[0067] The solvent is an ester solvent, an ether solvent, a mixed solvent of an alcohol solvent and water, or a mixed solvent of a ketone solvent and a saturated alkane solvent.

[0068] In one embodiment, the molar ratio of the phosphoric acid to the compound of formula I is 1.0-1.7, preferably 1.2.

[0069] In one embodiment, the molar ratio of the phosphoric acid to the compound shown in Formula I is (1.0-1.7):1; preferably 1.2:1.

[0070] In one embodiment, the molar volume ratio of the compound as shown in Formula I to the solvent is 0.11-0.21 mol / L, preferably 0.16 mol / L.

[0071] In one embodiment, in the mixed solvent of the alcohol solvent and water, the volume ratio of the alcohol solvent to the water is (14-24):1, preferably 19:1.

[0072] In a certain embodiment, in the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1.

[0073] In one embodiment, the solvent is a mixed solvent of IPA / H2O (19:1, v / v), a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether.

[0074] In a certain embodiment, the phosphate of the compound as shown in formula I is the phosphate crystal form B of the compound as shown in formula I, and the phosphate crystal form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 6.68±0.2°, 13.37±0.2°, 14.16±0.2°, 15.30±0.2°, 16.74±0.2°, and 20.12±0.2°.

[0075] In one embodiment, the phosphate crystal form B is an anhydrous crystal form.

[0076] In one embodiment, in the phosphate crystal form B, the molar ratio of the compound shown in formula I to phosphoric acid is 1:1.

[0077] In one embodiment, the phosphate crystal form B uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and also has diffraction peaks at one or more of the following locations: 3.35±0.2°, 14.53±0.2°, 21.26±0.2°, 22.53±0.2°, 24.42±0.2°, and 25.24±0.2°.

[0078] In one embodiment, the phosphate crystal form B uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and also has diffraction peaks at one or more of the following locations: 3.35±0.2°, 14.53±0.2°, 21.27±0.2°, 22.53±0.2°, 24.43±0.2°, and 25.24±0.2°.

[0079] In one embodiment, the phosphate crystal form B uses Cu-Kα radiation and has an X-ray powder diffraction pattern expressed in 2θ angles, with diffraction peaks at 6.68±0.2°, 13.37±0.2°, 14.16±0.2°, 14.53±0.2°, 15.30±0.2°, 16.74±0.2°, 20.12±0.2°, and 21.26±0.2°.

[0080] In one embodiment, the phosphate crystal form B uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and has diffraction peaks at 3.35±0.2°, 6.68±0.2°, 13.37±0.2°, 14.16±0.2°, 14.53±0.2°, 15.30±0.2°, 16.74±0.2°, 20.12±0.2°, 21.26±0.2°, 22.53±0.2°, 24.42±0.2°, and 25.24±0.2°.

[0081] In one embodiment, the phosphate crystal form B uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 4:

[0082] Table 4

[0083] Position.[°2θ] Relative strength.[%] Position.[°2θ] Relative strength.[%] 3.3488 100.00 21.4946 10.39 6.6843 21.93 21.7492 10.41 7.6346 4.49 22.5344 11.77 10.0305 3.43 23.0287 5.88 12.1675 7.90 23.2345 5.21 13.3734 45.72 23.9394 3.17 13.7627 11.36 24.4279 12.17 14.1560 9.48 25.2438 15.76 14.5261 7.21 25.6966 5.56 15.0409 11.28 27.0403 1.05 15.3041 34.26 27.8899 2.69 16.7414 68.50 28.7762 1.94 17.2869 7.43 29.6849 3.25 17.4813 8.70 32.1272 1.17 17.7801 12.25 32.7569 1.84 18.1056 17.31 33.5155 1.11 18.8004 4.56 34.5572 1.79 19.6890 4.68 35.9222 0.83 20.1204 23.28 36.8640 1.30 21.2684 20.03 In one embodiment, the phosphate crystal form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.11 shown.

[0084] The present invention also provides a method for preparing the phosphate crystal form B of the compound as shown in formula I, wherein the phosphate crystal form A is heated to 150±10° C. to obtain the phosphate crystal form B.

[0085] In one embodiment, the phosphate crystal form A is heated under nitrogen protection.

[0086] In one embodiment, the heating temperature is 145-155°C, preferably 150°C.

[0087] The present invention also provides a fumarate salt of the compound shown in formula I.

[0088] In one embodiment, the fumarate of the compound as shown in Formula I is a fumarate crystalline form A of the compound as shown in Formula I, and the fumarate crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 13.51±0.2°, 15.41±0.2°, 17.57±0.2°, 19.48±0.2°, and 20.11±0.2°.

[0089] In one embodiment, the fumarate salt form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and also has diffraction peaks at one or more of the following locations: 9.03±0.2°, 9.78±0.2°, 16.89±0.2°, 22.04±0.2°, 23.71±0.2°, 24.24±0.2°, and 25.72±0.2°.

[0090] In one embodiment, the fumarate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 9.03±0.2°, 9.78±0.2°, 13.51±0.2°, 15.41±0.2°, 16.89±0.2°, 17.57±0.2°, 19.48±0.2°, 20.11±0.2°, and 22.04±0.2°.

[0091] In one embodiment, the fumarate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 9.03±0.2°, 9.78±0.2°, 13.51±0.2°, 15.41±0.2°, 16.89±0.2°, 17.57±0.2°, 19.48±0.2°, 20.11±0.2°, 22.04±0.2°, 23.71±0.2°, 24.24±0.2°, and 25.72±0.2°.

[0092] In one embodiment, the fumarate salt crystalline form A is an anhydrous crystalline form.

[0093] In one embodiment, in the fumarate salt form A, the molar ratio of the compound shown in formula I to fumaric acid is 1:1.

[0094] In one embodiment, the fumarate salt form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 5:

[0095] Table 5

[0096]

[0097]

[0098] In one embodiment, the fumarate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.12 shown.

[0099] In one embodiment, the differential scanning calorimetry analysis diagram of the fumarate salt form A shows an endothermic peak starting point at 128.2±3°C.

[0100] In one embodiment, the fumarate salt form A has an endothermic peak at 130.3±3°C in its differential scanning calorimetry analysis diagram.

[0101] In one embodiment, the fumarate salt form A has a weight loss of about 1.17% at 150° C. in its thermogravimetric analysis diagram.

[0102] In one embodiment, the fumarate salt form A has a differential scanning calorimetry analysis diagram substantially as follows: Fig.14 shown.

[0103] In one embodiment, the thermogravimetric analysis diagram of the fumarate salt form A is substantially as follows: Fig.13 shown.

[0104] The present invention also provides a method for preparing a fumarate crystalline form A of a compound as shown in formula I, comprising mixing the compound as shown in formula I, fumaric acid and a solvent, and slurrying at room temperature to obtain the fumarate crystalline form A; the solvent is an ester solvent, an ether solvent, a mixed solvent of an alcohol solvent and water, or a mixed solvent of a ketone solvent and a saturated alkane solvent.

[0105] In one embodiment, the molar ratio of the fumaric acid to the compound of formula I is 1.0-1.5, preferably 1.0.

[0106] In one embodiment, the molar ratio of the fumaric acid to the compound of formula I is (1.0-1.5):1; preferably 1.0:1.

[0107] In one embodiment, the molar volume ratio of the compound represented by formula I to the solvent is 0.06-0.16 mol / L; preferably 0.11 mol / L;

[0108] In one embodiment, in the mixed solvent of the alcohol solvent and water, the volume ratio of the alcohol solvent to the water is (14-24):1, preferably 19:1.

[0109] In a certain embodiment, in the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1.

[0110] In one embodiment, the solvent is a mixed solvent of IPA / H2O (19:1, v / v), a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether.

[0111] The present invention also provides a p-toluenesulfonate salt of the compound as shown in formula I.

[0112] In a certain embodiment, the p-toluenesulfonate salt of the compound as shown in Formula I is the p-toluenesulfonate salt form A of the compound as shown in Formula I. In the p-toluenesulfonate salt form A, the p-toluenesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 5.41±0.2°, 8.10±0.2°, 14.74±0.2°, 17.13±0.2°, 18.10±0.2°, and 19.98±0.2°.

[0113] In one embodiment, the p-toluenesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following locations: 10.81±0.2°, 18.83±0.2°, 21.83±0.2°, and 24.37±0.2°.

[0114] In one embodiment, the p-toluenesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 5.41±0.2°, 7.74±0.2°, 8.10±0.2°, 10.81±0.2°, 14.74±0.2°, 17.13±0.2°, 18.10±0.2°, 18.83±0.2°, and 19.98±0.2°.

[0115] In one embodiment, the p-toluenesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 5.41±0.2°, 7.74±0.2°, 8.10±0.2°, 10.81±0.2°, 14.74±0.2°, 17.13±0.2°, 18.10±0.2°, 18.83±0.2°, 19.98±0.2°, 21.01±0.2°, 21.83±0.2°, 22.85±0.2°, 23.41±0.2°, 24.37±0.2°, 26.18±0.2°, and 28.58±0.2°.

[0116] In one embodiment, in the p-toluenesulfonate crystalline form A, the molar ratio of the compound represented by formula I to p-toluenesulfonic acid is 1:1.

[0117] In one embodiment, the p-toluenesulfonate salt form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 6:

[0118] Table 6

[0119] Position.[°2θ] Relative strength.[%] Position.[°2θ] Relative strength.[%] 5.4061 50.32 19.9778 61.40 7.7375 20.44 21.0061 12.71 8.1037 40.15 21.8329 62.62 10.8067 22.25 22.8534 30.96 13.1118 2.94 23.4116 26.46 14.7415 61.45 24.3701 39.55 15.2264 7.77 26.1763 17.86 16.2076 5.59 27.2507 6.34 17.1253 54.33 28.5791 19.45 18.1038 100.00 30.4321 3.98 18.3589 38.45 31.2458 6.35 18.8288 80.63

[0120] In one embodiment, the p-toluenesulfonate crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.16 shown.

[0121] In one embodiment, the p-toluenesulfonate crystalline form A has a differential scanning calorimetry analysis chart showing an endothermic peak starting point at 149.9±3°C.

[0122] In one embodiment, the p-toluenesulfonate crystalline form A has an endothermic peak at 152.1±3°C in its differential scanning calorimetry analysis chart.

[0123] In one embodiment, the p-toluenesulfonate crystalline form A has a weight loss of about 0.94% at 150° C. in its thermogravimetric analysis diagram.

[0124] In one embodiment, the p-toluenesulfonate crystalline form A has a differential scanning calorimetry analysis diagram substantially as follows: Fig.18 shown.

[0125] In one embodiment, the p-toluenesulfonate crystalline form A has a thermogravimetric analysis diagram substantially as follows: Fig.17 shown.

[0126] The present invention also provides a method for preparing the p-toluenesulfonate crystalline form A of the compound shown in formula I, comprising mixing the compound shown in formula I, p-toluenesulfonic acid, and a solvent, and slurrying at room temperature to obtain the p-toluenesulfonate crystalline form A;

[0127] The solvent is an ester solvent or an ether solvent.

[0128] In one embodiment, the molar ratio of p-toluenesulfonic acid to the compound of formula I is 1.0-1.5, preferably 1.0.

[0129] In one embodiment, the molar ratio of p-toluenesulfonic acid to the compound represented by formula I is (1.0-1.5):1; preferably 1.0:1.

[0130] In one embodiment, the molar volume ratio of the compound represented by formula I to the solvent is 0.06-0.16 mol / L; preferably 0.11 mol / L;

[0131] In one embodiment, the solvent is isopropyl acetate or methyl tert-butyl ether.

[0132] The present invention also provides a benzenesulfonate salt of the compound shown in formula I.

[0133] In a certain embodiment, the benzenesulfonate salt of the compound as shown in Formula I is the benzenesulfonate salt form A of the compound as shown in Formula I, and in the benzenesulfonate salt form A, the benzenesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 4.29±0.2°, 8.49±0.2°, 10.02±0.2°, 13.81±0.2°, and 15.26±0.2°.

[0134] In one embodiment, the benzenesulfonate salt form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and also has diffraction peaks at one or more of the following locations: 10.68±0.2°, 16.80±0.2°, 18.80±0.2°, 19.73±0.2°, 20.53±0.2°, and 20.99±0.2°.

[0135] In one embodiment, the benzenesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 4.29±0.2°, 8.49±0.2°, 10.02±0.2°, 10.68±0.2°, 13.81±0.2°, 15.26±0.2°, 16.80±0.2°, 18.80±0.2°, 19.73±0.2°, 20.53±0.2°, and 20.99±0.2°.

[0136] In one embodiment, the benzenesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 4.29±0.2°, 5.75±0.2°, 8.49±0.2°, 10.02±0.2°, 10.68±0.2°, 11.18±0.2°, 11.48±0.2°, 12.70±0.2°, 13.81±0.2°, 15.26±0.2°, 16.80±0.2°, 18.80±0.2°, 19.73±0.2°, 20.53±0.2°, 20.99±0.2°, 21.95±0.2°, and 23.90±0.2°.

[0137] In one embodiment, in the benzenesulfonate salt form A, the molar ratio of the compound as shown in formula I to benzenesulfonic acid is 1:1.

[0138] In one embodiment, the benzenesulfonate salt form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 7:

[0139] Table 7

[0140]

[0141]

[0142] In one embodiment, the benzenesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.19 shown.

[0143] In one embodiment, the benzenesulfonate salt form A has a differential scanning calorimetry analysis diagram showing an endothermic peak starting point at 144.5±3°C.

[0144] In one embodiment, the benzenesulfonate salt form A has an endothermic peak at 146.4±3°C in its differential scanning calorimetry analysis chart.

[0145] In one embodiment, the benzenesulfonate salt form A has a weight loss of about 1.28% at 140° C. in its thermogravimetric analysis diagram.

[0146] In one embodiment, the benzenesulfonate salt form A has a differential scanning calorimetry analysis diagram substantially as follows: Fig.21 shown.

[0147] In one embodiment, the benzenesulfonate salt form A has a thermogravimetric analysis diagram substantially as follows: Fig. 20 shown.

[0148] The present invention also provides a method for preparing the benzenesulfonate crystalline form A of the compound shown in formula I, comprising mixing the compound shown in formula I, benzenesulfonic acid, and a solvent, and slurrying at room temperature to obtain the benzenesulfonate crystalline form A;

[0149] The solvent is a mixed solvent of an ester solvent, an alcohol solvent and water.

[0150] In one embodiment, the molar ratio of the benzenesulfonic acid to the compound of formula I is 1.0-1.5, preferably 1.0.

[0151] In one embodiment, the molar ratio of the benzenesulfonic acid to the compound of formula I is (1.0-1.5); preferably 1.0:1.

[0152] In one embodiment, the molar volume ratio of the compound represented by formula I to the solvent is 0.06-0.16 mol / L; preferably 0.11 mol / L;

[0153] In one embodiment, in the mixed solvent of the alcohol solvent and water, the volume ratio of the alcohol solvent to the water is (14-24):1, preferably 19:1.

[0154] In one embodiment, the solvent is a mixed solvent of IPA / H2O (19:1, v / v) or isopropyl acetate.

[0155] The present invention also provides an oxalate of the compound shown in formula I.

[0156] In one embodiment, the oxalate of the compound as shown in Formula I is the oxalate crystal form A of the compound as shown in Formula I, and the oxalate crystal form A comprises the compound as shown in Formula I and oxalic acid;

[0157] Among them, the oxalate crystal form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and has diffraction peaks at 7.32±0.2°, 8.47±0.2°, 14.62±0.2°, 17.00±0.2°, 18.58±0.2°, and 19.44±0.2°.

[0158] In one embodiment, the oxalate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following locations: 12.93±0.2°, 13.47±0.2°, 15.23±0.2°, 22.38±0.2°, and 26.00±0.2°.

[0159] In one embodiment, the oxalate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 7.32±0.2°, 8.47±0.2°, 12.93±0.2°, 13.47±0.2°, 14.62±0.2°, 15.23±0.2°, 17.00±0.2°, 18.58±0.2°, 19.44±0.2°, 22.38±0.2°, and 26.00±0.2°.

[0160] In one embodiment, the oxalate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 4.64±0.2°, 7.32±0.2°, 8.47±0.2°, 12.93±0.2°, 13.47±0.2°, 14.62±0.2°, 15.23±0.2°, 17.00±0.2°, 18.05±0.2°, 18.58±0.2°, 19.44±0.2°, 20.57±0.2°, 21.49±0.2°, 22.38±0.2°, 23.26±0.2°, 23.59±0.2°, and 26.00±0.2°.

[0161] In one embodiment, the oxalate crystal form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 8:

[0162] Table 8

[0163] Position.[°2θ] Relative strength.[%] Position.[°2θ] Relative strength.[%] 4.6409 9.67 20.5689 32.57 7.3243 34.07 21.0873 24.03 8.4725 100.00 21.4883 39.50 12.9334 19.51 22.3807 86.67 13.4699 12.40 23.2608 31.24 14.6183 86.76 23.5935 30.33 15.2278 7.68 24.0272 21.48 16.9988 89.93 25.9955 32.08 18.0487 48.94 27.5449 4.60 18.5824 84.16 28.6854 3.47 18.8319 39.40 30.1750 12.59 19.4386 62.43 30.7971 5.66

[0164] In one embodiment, the oxalate crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.38 shown.

[0165] In one embodiment, the differential scanning calorimetry analysis diagram of the oxalate crystal form A may show a starting point of an endothermic peak at 151.3±3°C.

[0166] In one embodiment, the oxalate crystal form A has an endothermic peak at 153.6±3°C in its differential scanning calorimetry analysis diagram.

[0167] In one embodiment, the oxalate crystal form A has an endothermic peak at 162.8±3°C in its differential scanning calorimetry analysis diagram.

[0168] In one embodiment, the oxalate crystal form A has an endothermic peak at 218.8±3°C in its differential scanning calorimetry analysis diagram.

[0169] In one embodiment, the oxalate crystal form A has a weight loss of about 4.10% at 150° C. in its thermogravimetric analysis diagram.

[0170] In one embodiment, the oxalate crystal form A has a differential scanning calorimetry analysis diagram substantially as follows: Fig.40 shown.

[0171] In one embodiment, the thermogravimetric analysis diagram of the oxalate crystal form A is substantially as follows: Fig.39 shown.

[0172] In one embodiment, the oxalate of the compound of formula I is oxalate crystal form B of the compound of formula I, and in the oxalate crystal form B, the molar ratio of the compound of formula I to oxalic acid is 1:1;

[0173] Among them, the oxalate crystal form B uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, with diffraction peaks at 7.63±0.2°, 8.32±0.2°, 15.25±0.2°, 16.29±0.2°, 22.05±0.2°, and 23.84±0.2°.

[0174] In one embodiment, the oxalate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following locations: 12.47±0.2°, 17.66±0.2°, 18.26±0.2°, 18.77±0.2°, and 19.16±0.2°.

[0175] In one embodiment, the oxalate form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 7.63±0.2°, 8.32±0.2°, 12.47±0.2°, 15.25±0.2°, 16.29±0.2°, 17.66±0.2°, 18.26±0.2°, 18.77±0.2°, 19.16±0.2°, 22.05±0.2°, and 23.84±0.2°.

[0176] In one embodiment, the oxalate form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 7.63±0.2°, 8.32±0.2°, 12.47±0.2°, 15.25±0.2°, 16.29±0.2°, 17.66±0.2°, 18.26±0.2°, 18.77±0.2°, 19.16±0.2°, 19.92±0.2°, 20.83±0.2°, 21.28±0.2°, 22.05±0.2°, 23.84±0.2°, 25.05±0.2°, 26.40±0.2°, 27.41±0.2°, and 29.25±0.2°.

[0177] In one embodiment, in the oxalate crystal form B, the molar ratio of the compound as shown in formula I to oxalic acid is 1:1.

[0178] In one embodiment, the oxalate crystal form B uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 9:

[0179] Table 9

[0180] Position [°2θ] Relative strength [%] Position [°2θ] Relative strength [%] 7.6303 39.67 20.8286 39.95 8.3152 56.34 21.2807 28.72 12.4726 31.39 22.0493 70.88 15.2505 70.07 23.8443 93.78 16.2944 100.00 24.5635 18.67 17.6634 71.80 25.0476 23.37 18.2646 82.23 26.4010 16.45 18.4892 59.67 27.4132 20.10 18.7712 90.80 28.3635 5.97 19.1571 67.01 29.2511 13.78 19.9191 16.34

[0181] In one embodiment, the oxalate crystalline form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig. 22 shown.

[0182] In one embodiment, the oxalate crystal form B has a differential scanning calorimetry analysis diagram showing an endothermic peak starting point at 155.5±3°C.

[0183] In one embodiment, the oxalate crystal form B has an endothermic peak at 158.2±3°C in its differential scanning calorimetry analysis diagram.

[0184] In one embodiment, the oxalate crystal form B has an endothermic peak at 218.7±3°C in its differential scanning calorimetry analysis diagram.

[0185] In one embodiment, the oxalate crystal form B has a weight loss of about 1.21% at 150° C. in its thermogravimetric analysis diagram.

[0186] In one embodiment, the oxalate crystal form B has a differential scanning calorimetry analysis diagram substantially as follows: Fig.24 shown.

[0187] In one embodiment, the thermogravimetric analysis diagram of the oxalate crystal form B is substantially as follows: Fig.23 shown.

[0188] The present invention also provides a method for preparing the oxalate crystal form A of the compound as shown in formula I, comprising mixing the compound as shown in formula I, oxalic acid, and a solvent, and slurrying at room temperature to obtain the oxalate crystal form A;

[0189] The solvent is a mixed solvent of an alcohol solvent and water.

[0190] In one embodiment, the molar ratio of oxalic acid to the compound of formula I is 1.0-1.5, preferably 1.0.

[0191] In one embodiment, the molar ratio of oxalic acid to the compound of formula I is (1.0-1.5):1; preferably 1.0:1.

[0192] In a certain embodiment, in the mixed solvent of the alcohol solvent and water, the volume ratio of the alcohol solvent to the water is (14-24):1, preferably 19:1.

[0193] In one embodiment, the solvent is a mixed solvent of IPA / H2O (19:1, v / v).

[0194] The present invention also provides a method for preparing the oxalate crystal form B of the compound as shown in formula I, comprising mixing the compound as shown in formula I, oxalic acid, and a solvent, and slurrying at room temperature to obtain the oxalate crystal form B;

[0195] The solvent is a mixed solvent of an ester solvent, an ether solvent, a ketone solvent and a saturated alkane solvent.

[0196] In one embodiment, the molar ratio of oxalic acid to the compound represented by formula I is 1.0-1.5, preferably 1.0.

[0197] In one embodiment, the molar ratio of oxalic acid to the compound represented by formula I is (1.0-1.5):1; preferably 1.0:1.

[0198] In one embodiment, the molar volume ratio of the compound represented by formula I to the solvent is 0.02-0.08 mol / L; preferably 0.05 mol / L;

[0199] In a certain embodiment, in the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1.

[0200] In one embodiment, the solvent is a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether.

[0201] The present invention also provides a maleate salt of the compound shown in formula I.

[0202] In one embodiment, the maleate salt of the compound as shown in Formula I is the maleate salt form A of the compound as shown in Formula I, and the maleate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 13.54±0.2°, 16.92±0.2°, 17.64±0.2°, 19.61±0.2°, and 23.77±0.2°.

[0203] In one embodiment, the maleate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following locations: 3.44±0.2°, 9.64±0.2°, 18.08±0.2°, 20.82±0.2°, and 27.20±0.2°.

[0204] In one embodiment, the maleate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 3.44±0.2°, 9.64±0.2°, 13.54±0.2°, 16.92±0.2°, 17.64±0.2°, 18.08±0.2°, 19.61±0.2°, 20.82±0.2°, 23.77±0.2°, and 27.20±0.2°.

[0205] In one embodiment, the maleate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 3.44±0.2°, 9.64±0.2°, 13.54±0.2°, 16.92±0.2°, 17.64±0.2°, 18.08±0.2°, 19.61±0.2°, 20.82±0.2°, 22.36±0.2°, 22.71±0.2°, 23.77±0.2°, 27.20±0.2°, 28.90±0.2°, and 30.67±0.2°.

[0206] In one embodiment, in the maleate salt form A, the molar ratio of the compound as shown in formula I to maleic acid is 1:1.

[0207] In one embodiment, the maleate salt form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 10:

[0208] Table 10

[0209] Position [°2θ] Relative strength [%] Position [°2θ] Relative strength [%] 3.4417 16.32 21.6390 7.94 9.6432 27.14 22.3570 27.06 10.1448 5.95 22.7123 28.31 13.5352 100.00 23.7674 95.50 15.7013 7.54 24.4456 6.76 16.9220 49.89 24.8503 8.90 17.6360 60.94 25.5895 12.79 18.0813 36.58 26.7126 5.99 18.5713 13.66 27.2013 26.88 18.9912 11.46 27.7331 8.29 19.6099 51.55 28.8950 13.37 20.8195 31.63 30.6662 21.93

[0210] In one embodiment, the maleate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.25shown.

[0211] In one embodiment, the maleate salt form A has a differential scanning calorimetry analysis diagram showing an endothermic peak starting point at 123.4±3°C.

[0212] In one embodiment, the maleate salt form A has an endothermic peak at 125.2±3°C in its differential scanning calorimetry analysis diagram.

[0213] In one embodiment, the maleate salt form A has a weight loss of about 2.56% at 120° C. in its thermogravimetric analysis diagram.

[0214] In one embodiment, the maleate salt form A has a differential scanning calorimetry analysis diagram substantially as follows: Fig. 27 shown.

[0215] In one embodiment, the maleate salt form A has a thermogravimetric analysis diagram substantially as follows: Fig.26 shown.

[0216] The present invention also provides a method for preparing the maleate crystalline form A of the compound shown in formula I, comprising mixing the compound shown in formula I, maleic acid, and a solvent, and slurrying at room temperature to obtain the maleate crystalline form A;

[0217] The solvent is a mixed solvent of an ester solvent, an ether solvent, a ketone solvent and a saturated alkane solvent.

[0218] In one embodiment, the molar ratio of maleic acid to the compound of formula I is 1.0-1.5, preferably 1.0.

[0219] In one embodiment, the molar ratio of maleic acid to the compound of formula I is (1.0-1.5):1; preferably 1.0:1.

[0220] In a certain embodiment, in the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1.

[0221] In one embodiment, the solvent is a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether.

[0222] The present invention also provides a malate salt of the compound shown in formula I.

[0223] In one embodiment, the malate of the compound as shown in Formula I is malate crystalline form A of the compound as shown in Formula I, and the malate crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 8.95±0.2°, 9.89±0.2°, 13.21±0.2°, 16.53±0.2°, and 18.93±0.2°.

[0224] In one embodiment, the malate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 8.95±0.2°, 9.89±0.2°, 13.21±0.2°, 16.17±0.2°, 16.53±0.2°, 18.93±0.2°, and 24.77±0.2°.

[0225] In one embodiment, the malate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 6.63±0.2°, 8.95±0.2°, 9.89±0.2°, 13.21±0.2°, 16.17±0.2°, 16.53±0.2°, 18.93±0.2°, 21.62±0.2°, 23.20±0.2°, 23.80±0.2°, and 24.77±0.2°.

[0226] In one embodiment, in the malate crystalline form A, the molar ratio of the compound shown in formula I to malic acid is 1:1.

[0227] In one embodiment, the malate crystalline form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 11:

[0228] Table 11

[0229] Position [°2θ] Relative strength [%] Position [°2θ] Relative strength [%] 6.6262 7.38 19.7373 21.21 8.9534 20.94 21.6214 25.16 9.8936 38.20 23.1988 17.64 13.2054 50.38 23.8001 22.22 16.1763 29.75 24.7654 32.77 16.5259 50.45 27.2491 13.36 17.8951 33.19 31.4661 5.26 18.9290 100.00

[0230] In one embodiment, the malate crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.28 shown.

[0231] In one embodiment, the malate crystal form A has a differential scanning calorimetry analysis diagram showing an endothermic peak starting point at 86.3±3°C.

[0232] In one embodiment, the malate crystal form A has an endothermic peak at 96.3±3°C in its differential scanning calorimetry analysis diagram.

[0233] In one embodiment, the malate crystal form A has a weight loss of about 2.26% at 150° C. in its thermogravimetric analysis diagram.

[0234] In one embodiment, the malate crystal form A has a differential scanning calorimetry analysis diagram substantially as follows: Fig.30 shown.

[0235] In one embodiment, the malate crystal form A has a thermogravimetric analysis diagram substantially as follows: Fig.29 shown.

[0236] The present invention also provides a method for preparing the malate crystal form A of the compound shown in formula I, comprising mixing the compound shown in formula I, malic acid, and a solvent, and slurrying at room temperature to obtain the malate crystal form A;

[0237] The solvent is a mixed solvent of a ketone solvent and a saturated alkane solvent.

[0238] In one embodiment, the molar ratio of malic acid to the compound represented by formula I is 1.0-1.5, preferably 1.0.

[0239] In one embodiment, the molar ratio of malic acid to the compound represented by formula I is (1.0-1.5):1; preferably 1.0:1.

[0240] In a certain embodiment, in the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1, preferably 1:1.

[0241] In one embodiment, the solvent is a mixed solvent of acetone / n-heptane (1:1, v / v).

[0242] The present invention also provides a succinate salt of the compound shown in formula I.

[0243] In a certain embodiment, the succinate salt of the compound as shown in Formula I is the succinate salt form A of the compound as shown in Formula I, wherein the succinate salt form A has diffraction peaks at 6.94±0.2°, 9.20±0.2°, 13.87±0.2°, 16.29±0.2°, 17.94±0.2°, and 20.21±0.2° in an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles.

[0244] In one embodiment, the succinate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following locations: 14.70±0.2°, 17.40±0.2°, 19.48±0.2°, 20.96±0.2°, 22.18±0.2°, 23.04±0.2°, 23.92±0.2°, and 26.18±0.2°.

[0245] In one embodiment, the succinate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 6.94±0.2°, 9.20±0.2°, 13.87±0.2°, 16.29±0.2°, 17.94±0.2°, 20.21±0.2°, 20.96±0.2°, 22.18±0.2°, and 26.18±0.2°.

[0246] In one embodiment, the succinate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 6.94±0.2°, 9.20±0.2°, 13.87±0.2°, 14.70±0.2°, 16.29±0.2°, 17.40±0.2°, 17.94±0.2°, 19.48±0.2°, 20.21±0.2°, 20.96±0.2°, 22.18±0.2°, 23.04±0.2°, 23.92±0.2°, and 26.18±0.2°.

[0247] In one embodiment, in the succinate salt form A, the molar ratio of the compound as shown in formula I to succinic acid is 1:1.

[0248] In one embodiment, the X-ray powder diffraction pattern of the succinate salt form A using Cu-Kα radiation and expressed in 2θ angles comprises diffraction peak positions and relative intensities substantially as shown in Table 12:

[0249] Table 12

[0250]

[0251]

[0252] In one embodiment, in the succinate salt form A, the molar ratio of the compound as shown in formula I to succinic acid is 1:1.2, 1:1.1 or 1:1.

[0253] In one embodiment, the succinate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.31 shown.

[0254] In one embodiment, the differential scanning calorimetry analysis diagram of the succinate salt form A shows an endothermic peak starting point at 75.9±3°C.

[0255] In one embodiment, the succinate salt form A has an endothermic peak at 85.4±3°C in its differential scanning calorimetry analysis diagram.

[0256] In one embodiment, the succinate salt form A has a weight loss of about 4.49% at 150° C. in its thermogravimetric analysis diagram.

[0257] In one embodiment, the differential scanning calorimetry analysis diagram of the succinate salt form A is substantially as follows: Fig.33 shown.

[0258] In one embodiment, the succinate crystal form A has a thermogravimetric analysis diagram substantially as follows: Fig.32 shown.

[0259] The present invention also provides a method for preparing the succinate crystal form A of the compound shown in formula I, comprising mixing the compound shown in formula I, succinic acid, and a solvent, and slurrying at room temperature to obtain the succinate crystal form A;

[0260] The solvent is an ether solvent.

[0261] In one embodiment, the molar ratio of succinic acid to the compound represented by formula I is 1.0-1.5, preferably 1.0.

[0262] In one embodiment, the molar ratio of succinic acid to the compound represented by formula I is (1.0-1.5):1; preferably 1.0:1.

[0263] In one embodiment, the solvent is methyl tert-butyl ether.

[0264] The present invention also provides a mesylate salt of the compound shown in formula I.

[0265] In a certain embodiment, the mesylate salt of the compound as shown in Formula I is the mesylate salt form A of the compound as shown in Formula I, wherein the mesylate salt form A has diffraction peaks at 5.03±0.2°, 17.03±0.2°, 18.11±0.2°, 20.60±0.2°, and 23.40±0.2° in an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles.

[0266] In one embodiment, the mesylate salt form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 13:

[0267] Table 13

[0268] Position.[°2θ] Relative strength.[%] Position.[°2θ] Relative strength.[%] 5.0258 56.54 20.5965 100.00 17.0335 38.98 23.3964 71.59 18.1100 61.40

[0269] In one embodiment, the mesylate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.34 shown.

[0270] In a certain embodiment, the mesylate salt of the compound as shown in Formula I is the mesylate salt form B of the compound as shown in Formula I, and the mesylate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 18.89±0.2°, 20.43±0.2°, 21.07±0.2°, 23.44±0.2°, and 24.46±0.2°.

[0271] In one embodiment, the mesylate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following locations: 9.76±0.2°, 11.32±0.2°, 15.46±0.2°, and 17.26±0.2°.

[0272] In one embodiment, the mesylate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following locations: 9.83±0.2°, 11.32±0.2°, 15.46±0.2°, and 17.26±0.2°.

[0273] In one embodiment, the mesylate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 9.76±0.2°, 11.32±0.2°, 15.46±0.2°, 17.26±0.2°, 18.89±0.2°, 20.43±0.2°, 21.07±0.2°, 23.44±0.2°, and 24.46±0.2°.

[0274] In one embodiment, the mesylate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 9.83±0.2°, 11.32±0.2°, 15.46±0.2°, 17.26±0.2°, 18.89±0.2°, 20.43±0.2°, 21.07±0.2°, 23.44±0.2°, and 24.46±0.2°.

[0275] In one embodiment, the mesylate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 9.76±0.2°, 11.32±0.2°, 15.46±0.2°, 16.98±0.2°, 17.26±0.2°, 17.63±0.2°, 18.89±0.2°, 19.68±0.2°, 20.43±0.2°, 21.07±0.2°, 21.58±0.2°, 22.09±0.2°, 22.69±0.2°, 23.44±0.2°, and 24.46±0.2°.

[0276] In one embodiment, the mesylate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 9.83±0.2°, 11.32±0.2°, 15.46±0.2°, 16.98±0.2°, 17.26±0.2°, 17.63±0.2°, 18.89±0.2°, 19.68±0.2°, 20.43±0.2°, 21.07±0.2°, 21.58±0.2°, 22.09±0.2°, 22.69±0.2°, 23.44±0.2°, and 24.46±0.2°.

[0277] In one embodiment, in the mesylate salt form B, the molar ratio of the compound as shown in formula I to methanesulfonic acid is 1:2.

[0278] In one embodiment, the mesylate salt form B uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and the diffraction peak positions and relative intensities thereof are substantially as shown in Table 14:

[0279] Table 14

[0280]

[0281]

[0282] In one embodiment, in the mesylate salt form B, the molar ratio of the compound as shown in formula I to methanesulfonic acid is 1:2.1 or 1:2.

[0283] In one embodiment, the mesylate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.35 shown.

[0284] In one embodiment, the mesylate salt form B has a differential scanning calorimetry analysis chart showing an endothermic peak starting point at 97.3±3°C.

[0285] In one embodiment, the mesylate salt form B has an endothermic peak at 109.4±3°C in its differential scanning calorimetry analysis chart.

[0286] In one embodiment, the mesylate salt form B has a thermogravimetric analysis chart showing a weight loss of about 0.91% at 80°C and a weight loss of about 2.40% at 80-130°C.

[0287] In one embodiment, the mesylate salt form B has a differential scanning calorimetry analysis diagram substantially as follows: Fig.37 shown.

[0288] In one embodiment, the mesylate salt form B has a thermogravimetric analysis diagram substantially as follows: Fig.36 shown.

[0289] The present invention also provides a method for preparing the mesylate crystal form A of the compound shown in formula I, comprising mixing the compound shown in formula I, methanesulfonic acid, and a solvent, and slurrying at room temperature to obtain the mesylate crystal form A;

[0290] The solvent is a mixed solvent of a ketone solvent and a saturated alkane solvent.

[0291] In one embodiment, the molar ratio of the methanesulfonic acid to the compound represented by formula I is (1.0-1.2):1; preferably 1:1.

[0292] In a certain embodiment, in the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1, preferably 1:1.

[0293] In one embodiment, the solvent is a mixed solvent of acetone / n-heptane (1:1, v / v).

[0294] The present invention also provides a method for preparing the mesylate crystal form B of the compound as shown in formula I, comprising mixing the compound as shown in formula I, methanesulfonic acid, and a solvent, and slurrying at room temperature to obtain the mesylate crystal form B;

[0295] The solvent is a mixed solvent of an ester solvent, an ether solvent, a ketone solvent and a saturated alkane solvent.

[0296] In one embodiment, the molar ratio of the methanesulfonic acid to the compound represented by formula I is (1.5-2.5):1; preferably 2:1.

[0297] In a certain embodiment, in the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1.

[0298] In one embodiment, the solvent is a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether.

[0299] The present invention also provides a 2-hydroxyethanesulfonate salt of the compound shown in formula I.

[0300] In a certain embodiment, the 2-hydroxyethanesulfonate of the compound as shown in Formula I is the 2-hydroxyethanesulfonate crystalline form A of the compound as shown in Formula I, and the 2-hydroxyethanesulfonate crystalline form A uses Cu-Kα radiation and an X-ray powder diffraction pattern expressed in 2θ angles, and has diffraction peaks at 4.85±0.2°, 9.85±0.2°, 10.98±0.2°, 18.09±0.2°, 19.35±0.2°, and 20.33±0.2°.

[0301] In one embodiment, the 2-hydroxyethanesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at one or more of the following positions: 15.54±0.2°, 15.94±0.2°, 21.83±0.2°, 22.33±0.2°, and 22.87±0.2°.

[0302] In one embodiment, the 2-hydroxyethanesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 4.85±0.2°, 9.85±0.2°, 10.98±0.2°, 15.54±0.2°, 15.94±0.2°, 18.09±0.2°, 19.35±0.2°, 20.33±0.2°, 21.83±0.2°, 22.33±0.2°, and 22.87±0.2°.

[0303] In one embodiment, the 2-hydroxyethanesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, and has diffraction peaks at 4.85±0.2°, 9.85±0.2°, 10.98±0.2°, 12.83±0.2°, 15.54±0.2°, 15.94±0.2°, 16.66±0.2°, 18.09±0.2°, 19.35±0.2°, 20.33±0.2°, 21.83±0.2°, 22.33±0.2°, and 22.87±0.2°.

[0304] In one embodiment, in the 2-hydroxyethanesulfonate salt form A, the molar ratio of the compound shown in formula I to 2-hydroxyethanesulfonic acid is 1:1.

[0305] In one embodiment, the X-ray powder diffraction pattern of the 2-hydroxyethanesulfonate salt form A using Cu-Kα radiation and expressed in 2θ angles comprises diffraction peak positions and relative intensities substantially as shown in Table 15:

[0306] Table 15

[0307] Position.[°2θ] Relative strength.[%] Position.[°2θ] Relative strength.[%] 4.8473 97.56 20.3297 56.13 9.8479 49.33 21.8277 45.05 10.9792 82.75 22.3258 67.31 12.8290 12.79 22.8682 63.84 14.2549 4.53 24.9854 21.98 15.5419 25.71 26.2466 10.34 15.9356 30.48 26.9452 8.37 16.6623 12.53 28.5116 17.43 18.0907 88.25 31.1759 4.85 19.3520 100.00

[0308] In one embodiment, the 2-hydroxyethanesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles as follows: Fig.41 shown.

[0309] In one embodiment, the differential scanning calorimetry analysis diagram of the 2-hydroxyethanesulfonate salt form A shows an endothermic peak starting point at 109.5±3°C.

[0310] In one embodiment, the 2-hydroxyethanesulfonate salt form A has an endothermic peak at 118.4±3° C. in its differential scanning calorimetry analysis chart.

[0311] In one embodiment, the 2-hydroxyethanesulfonate salt form A has a weight loss of about 1.28% at 110° C. in its thermogravimetric analysis.

[0312] In one embodiment, the 2-hydroxyethanesulfonate salt form A has a differential scanning calorimetry analysis diagram substantially as follows: Fig.43 shown.

[0313] In one embodiment, the 2-hydroxyethanesulfonate salt form A has a thermogravimetric analysis diagram substantially as follows: Fig.42 shown.

[0314] The present invention also provides a method for preparing the 2-hydroxyethanesulfonate crystalline form A of the compound shown in formula I, comprising mixing the compound shown in formula I, 2-hydroxyethanesulfonic acid, and a solvent, and slurrying at room temperature to obtain the 2-hydroxyethanesulfonate crystalline form A;

[0315] The solvent is a mixed solvent of an ester solvent, a ketone solvent and a saturated alkane solvent.

[0316] In one embodiment, the molar ratio of the 2-hydroxyethanesulfonic acid to the compound represented by formula I is (1.5-2.5):1; preferably 2:1.

[0317] In a certain embodiment, in the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1.

[0318] In one embodiment, the solvent is a mixed solvent of acetone / n-heptane (1:1, v / v) or isopropyl acetate.

[0319] The present invention also provides a pharmaceutical composition, comprising any of the above-mentioned crystal forms or salt forms of the compound as shown in Formula I, and at least one pharmaceutical excipient.

[0320] The selection of the pharmaceutical excipients varies depending on the route of administration and the characteristics of the action, and can generally be conventional fillers, diluents, binders, wetting agents, disintegrants, lubricants, emulsifiers, suspending agents, etc. in the art.

[0321] The present invention also provides a use of a substance M, wherein the substance M is a crystalline form, a salt form or the pharmaceutical composition of any one of the above compounds as shown in Formula I.

[0322] The uses include:

[0323] 1) Inhibit tubulin polymerization and / or Src kinase;

[0324] 2) Preventing and / or treating diseases related to tubulin polymerization and / or Src kinase;

[0325] 3) Preparation of tubulin polymerization and / or Src kinase inhibitors;

[0326] 4) Preparation of drugs or preparations for preventing and / or treating diseases related to tubulin polymerization and / or Src kinase.

[0327] Preferably, the uses include: inhibiting tubulin polymerization; and / or preventing and / or treating diseases mediated by tubulin polymerization; and / or preparing tubulin polymerization inhibitors, and / or preventing and / or treating drugs, pharmaceutical compositions or preparations for diseases mediated by tubulin polymerization.

[0328] Preferably, the use includes: inhibiting Src kinase; and / or preventing and / or treating diseases mediated by Src kinase; and / or preparing Src kinase inhibitors; and / or preparing drugs, pharmaceutical compositions or preparations for preventing and / or treating diseases mediated by Src kinase.

[0329] Preferably, the drug is an external preparation.

[0330] Preferably, the drug is a transdermal drug.

[0331] Preferably, the diseases associated with tubulin polymerization and / or Src kinase include tumors and skin diseases.

[0332] The present invention also provides a use of a substance M, wherein the substance M is a crystalline form, a salt form or the pharmaceutical composition of any one of the above compounds as shown in Formula I.

[0333] The use is use in preparing medicines for treating or preventing tumors and / or skin diseases.

[0334] Preferably, the tumor includes: solid tumor, sarcoma, hematological cancer;

[0335] More preferably, the tumor includes: breast cancer, ovarian cancer, prostate cancer, cervical cancer, testicular cancer, colon cancer, colorectal cancer, liver cancer, non-small cell lung cancer, squamous cell carcinoma (e.g., cutaneous squamous cell carcinoma), small cell lung cancer, gastric cancer, gastrointestinal stromal tumor, pancreatic cancer, bladder cancer, germ cell tumor, mast cell tumor, mastocytosis, glioblastoma, neuroblastoma, astrocytoma, melanoma, B cell lymphoma, T cell lymphoma, slowly progressive lymphoma, Hodgkin lymphoma, non-Hodgkin lymphoma, acute myeloid leukemia, acute lymphocytic leukemia, chronic myeloid leukemia, chronic lymphocytic leukemia, myeloma and / or myelodysplastic syndrome.

[0336] Preferably, the skin disease includes actinic keratosis, psoriasis, atopic dermatitis, psoriasis, vitiligo, roseola and / or systemic lupus erythematosus.

[0337] Preferably, the drug is an external preparation.

[0338] Preferably, the drug is a transdermal drug.

[0339] The present invention also provides a use of at least one of the crystal forms or salt forms of the compound as shown in Formula I for treating or preventing tumors and / or skin diseases.

[0340] Preferably, the tumor includes: solid tumor, sarcoma, hematological cancer;

[0341] More preferably, the tumor includes: breast cancer, ovarian cancer, prostate cancer, cervical cancer, testicular cancer, colon cancer, colorectal cancer, liver cancer, non-small cell lung cancer, squamous cell carcinoma (e.g., cutaneous squamous cell carcinoma), small cell lung cancer, gastric cancer, gastrointestinal stromal tumor, pancreatic cancer, bladder cancer, germ cell tumor, mast cell tumor, mastocytosis, glioblastoma, neuroblastoma, astrocytoma, melanoma, B cell lymphoma, T cell lymphoma, slowly progressive lymphoma, Hodgkin lymphoma, non-Hodgkin lymphoma, acute myeloid leukemia, acute lymphocytic leukemia, chronic myeloid leukemia, chronic lymphocytic leukemia, myeloma and / or myelodysplastic syndrome.

[0342] Preferably, the skin disease includes actinic keratosis, psoriasis, atopic dermatitis, psoriasis, vitiligo, roseola and / or systemic lupus erythematosus.

[0343] The present invention also provides a method for inhibiting Src kinase, or preventing and / or treating Src kinase-related (or mediated) diseases, comprising the steps of: administering the above-mentioned crystal form and / or salt form to a subject in need thereof.

[0344] The present invention also provides a method for inhibiting tubulin, or preventing and / or treating diseases associated with (or mediated by) tubulin, comprising the steps of: administering the crystal form and / or salt form of the present invention to a subject in need thereof.

[0345] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0346] the term

[0347] When the terms "about" and "approximately" are used in reference to XRPD peaks, these terms mean that the error of the referenced X-ray powder diffraction peak position [°2θ] is: ±0.3, ±0.2 or ±0.1, preferably ±0.2, more preferably ±0.1.

[0348] When referring to XRPD peak positions, 2θ angles may be rounded to 2 or 4 significant figures after the decimal point.

[0349] When the terms "about" and "approximately" are used in reference to temperature or temperature range, these terms mean that the error of the referenced temperature or temperature range is: ±5°C, ±3°C, ±2°C, or ±1°C, preferably ±3°C.

[0350] The reagents and raw materials used in the present invention are commercially available.

[0351] The positive and progressive effects of the present invention are: a compound and salt form and crystal form for a tubulin-SRC dual-target inhibitor, wherein the compound has a structure of Formula I as described in the present invention. The compound and salt form and crystal form can be used as a tubulin and Src kinase dual-target inhibitor, or as a single tubulin or Src kinase inhibitor. The compound of the present invention can significantly inhibit the polymerization of tubulin monomers and inhibit cell proliferation. It has good pharmacokinetic properties for topical administration to the skin and good drugability. It can be used to prepare a skin topical preparation, and has the advantages of fast metabolism and small side effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0352] Figure 1 XRPD pattern of free form A;

[0353] Figure 2 TGA diagram of free form A;

[0354] Figure 3 DSC diagram of free form A;

[0355] Figure 4 XRPD pattern of free form B;

[0356] Figure 5 TGA diagram of free form B;

[0357] Figure 6 DSC diagram of free form B;

[0358] Figure 7 XRPD pattern of phosphate crystal form A;

[0359] Figure 8 TGA diagram of phosphate crystal form A;

[0360] Fig. 9 DSC graph of phosphate crystal form A;

[0361] Fig.10 VT-XRPD pattern of phosphate form A;

[0362] Fig.11 XRPD pattern of phosphate form B;

[0363] Fig.12 XRPD pattern of fumarate salt Form A;

[0364] Fig.13 TGA diagram of fumarate salt form A;

[0365] Fig.14 DSC graph of fumarate salt form A;

[0366] Fig.15 VH-XRPD pattern of fumarate salt Form A;

[0367] Fig.16 XRPD pattern of p-toluenesulfonate salt Form A;

[0368] Fig.17 TGA diagram of p-toluenesulfonate Form A;

[0369] Fig.18 DSC diagram of p-toluenesulfonate Form A;

[0370] Fig.19 XRPD pattern of benzenesulfonate salt Form A;

[0371] Fig. 20 TGA diagram of benzenesulfonate salt form A;

[0372] Fig.21 DSC graph of benzenesulfonate salt form A;

[0373] Fig. 22 XRPD pattern of oxalate form B;

[0374] Fig.23 TGA diagram of oxalate form B;

[0375] Fig.24 DSC graph of oxalate form B;

[0376] Fig.25 XRPD pattern of maleate salt Form A;

[0377] Fig.26 TGA diagram of maleate salt form A;

[0378] Fig. 27 DSC graph of maleate salt form A;

[0379] Fig.28 XRPD pattern of malate Form A;

[0380] Fig.29 TGA diagram of malate form A;

[0381] Fig.30 DSC graph of malate form A;

[0382] Fig.31 XRPD pattern of succinate salt Form A;

[0383] Fig.32 TGA diagram of succinate salt form A;

[0384] Fig.33 DSC graph of succinate salt form A;

[0385] Fig.34 XRPD pattern of mesylate salt Form A;

[0386] Fig.35 XRPD pattern of mesylate salt Form B;

[0387] Fig.36 TGA diagram of mesylate salt Form B;

[0388] Fig.37 DSC graph of mesylate Form B;

[0389] Fig.38 XRPD pattern of oxalate form A;

[0390] Fig.39 TGA diagram of oxalate form A;

[0391] Fig.40 DSC graph of oxalate form A;

[0392] Fig.41 XRPD pattern of 2-hydroxyethanesulfonate salt Form A;

[0393] Fig.42 TGA diagram of 2-hydroxyethanesulfonate Form A;

[0394] Fig.43 DSC graph of 2-hydroxyethanesulfonate Form A;

[0395] Fig.44 Dynamic solubility curve in water at 37°C;

[0396] Fig.45 Dynamic solubility curve in SGF at 37°C;

[0397] Fig.46 Dynamic solubility curve in FaSSIF at 37°C;

[0398] Fig.47 Dynamic solubility curve in FeSSIF at 37°C;

[0399] Fig.48 DVS diagram of free form A;

[0400] Fig.49 XRPD overlay of free form A before and after DVS test;

[0401] Fig.50 DVS diagram of phosphate crystal form A;

[0402] Fig.51 XRPD overlay of phosphate crystal form A before and after DVS testing;

[0403] Fig.52 DVS diagram of fumarate salt form A;

[0404] Fig.53 XRPD overlay of fumarate salt form A before and after DVS testing;

[0405] Fig.54 DVS diagram of p-toluenesulfonate Form A;

[0406] Fig.55 XRPD overlay of p-toluenesulfonate Form A before and after DVS testing;

[0407] Fig.56 DVS diagram of benzenesulfonate salt form A;

[0408] Fig.57 XRPD overlay of benzenesulfonate salt form A before and after DVS testing;

[0409] Fig.58 DVS diagram of oxalate form B;

[0410] Fig.59 XRPD overlay of oxalate form B before and after DVS testing;

[0411] Fig.60 XRPD overlay of the stability evaluation sample of free form A;

[0412] Fig.61 XRPD overlay of the phosphate crystal form A stability assessment sample;

[0413] Fig.62 XRPD overlay of the stability evaluation sample of the fumarate salt form A;

[0414] Fig.63 XRPD overlay of the p-toluenesulfonate Form A stability assessment sample;

[0415] Fig.64 XRPD overlay of the stability evaluation sample of benzenesulfonate Form A;

[0416] Fig.65 XRPD overlay of the stability evaluation sample of oxalate Form B;

[0417] Fig.66 The results of the test on the inhibition of tubulin polymerization by the compound shown in Formula I;

[0418] Fig.67 p-SRC inhibitory activity experimental results. DETAILED DESCRIPTION

[0419] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0420] Instrument information and methods

[0421] 1. X-ray powder diffraction (XRPD)

[0422] The XRPD pattern was collected on an X-ray powder diffraction analyzer produced by PANalytacal, and the scanning parameters are shown in Table 16.

[0423] Table 16 XRPD test parameters

[0424]

[0425] 2. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC)

[0426] The TGA and DSC graphs were collected on a TA 5500 thermogravimetric analyzer and a TA 2500 differential scanning calorimeter, respectively. Table 17 lists the test parameters.

[0427] Table 17 TGA and DSC test parameters

[0428] parameter TGA DSC method Linear temperature rise Linear temperature rise Sample tray Aluminum tray, open Aluminum tray, with cover or without cover Temperature range Room temperature - set the end point temperature 25℃-Set the end temperature Purge rate (℃ / min) 10 10 Protective gas Nitrogen Nitrogen

[0429] 3. Dynamic moisture sorption (DVS)

[0430] Dynamic moisture sorption (DVS) curves were collected on the DVSIntrInsic of SMS (Surface Measurement Systems). The relative humidity at 25°C was corrected using the deliquescent points of LiCl, Mg(NO3)2 and KCl. The DVS test parameters are listed in Table 18.

[0431] Table 18 DVS test parameters

[0432]

[0433] 4. Polarized Light Microscopy (PLM)

[0434] Polarized light microscopy images were taken at room temperature using a Zeiss Axio Scope.A1 microscope.

[0435] 5. Liquid NMR ( 1 H NMR)

[0436] Liquid-state NMR spectra were collected on a Bruker 400M NMR instrument using DMSO-d6 or CD3OD as solvent.

[0437] 6. High Performance Liquid Chromatography and Ion Chromatography (HPLC / IC)

[0438] In the experiment, the purity test, dynamic solubility and stability test were tested by Agilent 1260 high performance liquid chromatograph, and the ion salt formation molar ratio test was tested by ion chromatography. The analysis conditions are shown in Tables 19 and 20.

[0439] Table 19 HPLC test conditions

[0440]

[0441]

[0442] Table 20 Ion chromatography test conditions

[0443] Ion Chromatography ThermoFisher ICS-1100 Chromatographic columns IonPac AS18 Analytical Column,250*4mm Mobile phase 25mM NaOH Injection volume 25μL Flow rate 1.0mL / min temperature 35℃ Column temperature 35℃ Current 80mA Run time 20min

[0444] Solvent Chinese and English comparison table

[0445] The abbreviations of the solvents and their corresponding Chinese names are shown in Table 21.

[0446] Table 21 Comparison table of Chinese and English names of solvents used in the test

[0447]

[0448]

[0449] Preparation of the compound shown in formula I

[0450] The synthetic route is as follows:

[0451]

[0452] Step 1: Synthesis of 1-bromo-4-(2-bromoethoxy)-2-methylbenzene

[0453] 4-Bromo-3-methylphenol (1 g, 5.37 mmol), 1,2-dibromoethane (5.99 g, 32.2 mmol) and potassium carbonate (4.45 g, 32.2 mmol) were dissolved in acetone (30 mL), heated to 80°C and refluxed for 18 hours. The mixture was cooled to room temperature, filtered, and the filtrate was concentrated. The residue was separated by column chromatography (petroleum ether: ethyl acetate (V / V) = 30:1) to obtain 1-bromo-4-(2-bromoethoxy)-2-methylbenzene (1.3 g, colorless oil, yield 82.8%).

[0454] Step 2: (3aR,6aS)-5-(2-(4-bromo-3-methylphenoxy)ethyl)hexahydro-1H-furano[3,4-c]pyrrole

[0455] 1-Bromo-4-(2-bromoethoxy)-2-methylbenzene (1.3 g, 4.45 mmol) was dissolved in dry acetonitrile (30 mL), (3aR, 6aS)-hexahydro-1H-furano[3,4-c]pyrrole hydrochloride (730 mg, 4.90 mmol) and potassium carbonate (1.844 g, 13.36 mmol) were added, and the temperature was raised to 80°C for 20 hours. The reaction solution was cooled to room temperature, filtered, and the filtrate was concentrated. The residue was purified by silica gel column (petroleum ether: ethyl acetate (V / V) = 1:1) to obtain (3aR, 6aS)-5-(2-(4-bromo-3-methylphenoxy)ethyl)hexahydro-1H-furano[3,4-c]pyrrole (1.0 g, yellow oil, yield 69.1%).

[0456] LC-MS, M / Z (ESI): 326.0 [M+H] + .

[0457] Step 3: N-benzyl-2-(5-(2-methyl-4-(2-((3aR,6aS)-tetrahydro-1H-furan[3,4-c]pyrrol-5(3H)-yl)ethoxy)phenyl)pyridin-2-yl)acetamide (I)

[0458]

[0459] (3aR, 6aS)-5-(2-(4-bromo-3-methylphenoxy)ethyl)hexahydro-1H-furano[3,4-c]pyrrole (150 mg, 0.460 mmol) was dissolved in dry 1,4-dioxane (5 mL), and N-benzyl-2-(5-(tributylstannyl)pyridin-2-yl)acetamide (355 mg, 0.690 mmol) and bis(triphenylphosphino)palladium dichloride (32.3 mg, 0.046 mmol) were added. The argon atmosphere was replaced three times, and the temperature was raised to 100°C under argon protection for 4 hours. The reaction solution was cooled to room temperature, diluted with water (50 mL), extracted with dichloromethane (50 mL×3), the organic phases were combined, dried over anhydrous sodium sulfate, concentrated, and the residue was separated on a silica gel plate (ethyl acetate:methanol (V / V)=20:1, NH3·H2O) to obtain N-benzyl-2-(5-(2-methyl-4-(2-((3aR,6aS)-tetrahydro-1H-furan[3,4-c]pyrrol-5(3H)-yl)ethoxy)phenyl)pyridin-2-yl)acetamide (compound shown in Formula I) (20 mg, yield 9.22%), i.e., an amorphous solid of the compound of Formula I.

[0460] 1 H NMR (400MHz, DMSO-d6): δ8.62(t, 1H), 8.41(d, 1H), 7.70~6.83(m, 10H), 4.30(d, 2H), 4.07(t, 2H), 3.78~3.62(m, 4H), 3.39~3.37(m, 2H), 2.75~2.61(m, 6H), 2.39~2.37(m, 2H), 2.21(s, 3H).

[0461] LC-MS, M / Z (ESI): 472.2 [M+H] + .

[0462] Example 1 Free Form A

[0463] Preparation of free crystal form A:

[0464] The compound of formula I was stirred and dissolved in THF solution at room temperature, filtered after dissolution, and slowly evaporated at room temperature to obtain free crystalline form A. The solid was dried in vacuum at room temperature and characterized by XRPD and TGA / DSC.

[0465] The XRPD and TGA / DSC characterization results of the free form A sample are as follows: Figure 1-3The XRPD diffraction peak data of free crystalline form A are shown in Table 22. The TGA results show that the sample has a weight loss of 0.98% when the temperature rises to 150°C. The DSC results show that the sample has an endothermic peak at 96.6°C, and the starting temperature is 94.7°C. The TGA weight loss of free crystalline form A is low, and DSC has only a single melting signal. The free crystalline form A is anhydrous crystalline form. 1 H NMR was collected using CD3OD as solvent, and the specific data are shown below.

[0466] 1 H NMR (400MHz, CD3OD): δ8.40(1H,d),7.74(1H,dd),7.44(1H,d),7.33~7.28(4H,m),7.26~7.23(1H,m),7.15(1H,d),6.91(1H,d) ,6.86(1H,dd),4.42(2H,s),4.15(2H,t),3.82(2H,s),3.71~3.64(4H,m),3.02(2H,t),2.86(4H,t),2.33(2H,dd),2.25(3H,s).

[0467] Table 22 XRPD diffraction peak data of free form A

[0468]

[0469]

[0470] Example 2 Free Form B

[0471] The free crystalline form B sample is obtained by dissolving the compound shown in Formula I in MeOH and then removing the solvent by rotary evaporation under reduced pressure, and then drying the obtained colloidal sample under vacuum at 50°C. The XRPD and TGA / DSC characterization results are shown in Figure 4-6 As shown, the XRPD diffraction peak data of the free crystalline form B are shown in Table 23. The TGA results show that the sample has a weight loss of 0.48% when the temperature is increased to 150°C, and the DSC results show that the sample has two endothermic peaks at 84.5°C and 92.4°C (peak temperature). 1 The H NMR results are shown below. From the NMR data, it can be seen that no MeOH residue is observed in the Form B sample. The TGA weight loss of the free Form B is low, and the free Form B is anhydrous. The free Form B is heated to 86°C, cooled to room temperature and exposed to air, and the sample is converted to the free Form A.

[0472] 1H NMR (400MHz, CD3OD): δ8.66(1H,t),8.44(1H,d),7.71(1H,d),7.41~7.14(7H,m),6.92(1H,s),6.87(1H,d ),4.32(2H,d),4.09(2H,t),3.73(4H,m),3.41~3.39(2H,m),2.77~2.63(6H,m),2.39(2H,m),2.23(3H,s).

[0473] Table 23 XRPD diffraction peak data of free form B

[0474] Position [°2θ] Relative strength [%] Position [°2θ] Relative strength [%] 7.4873 3.10 22.6576 61.87 8.8864 9.12 23.9201 7.02 10.9912 18.04 24.7970 12.05 13.8121 14.37 25.4143 15.92 14.9693 6.34 26.6488 16.69 16.1011 36.37 27.7637 6.02 16.5486 39.23 28.3501 3.63 16.9933 5.23 29.5259 2.44 17.7740 100.00 30.7717 5.46 18.6972 5.30 31.9792 2.29 19.6520 31.67 33.3167 3.42 20.3614 65.65 37.7157 3.02 21.2371 58.26 39.0657 1.38 22.0673 19.39

[0475] Example 3 Study on the transformation relationship between free state crystal forms

[0476] In order to further study the transformation relationship between free crystalline form A and free crystalline form B, suspension competition experiments between free crystalline form A and free crystalline form B were set up in CPME and IPAc systems at room temperature and 50°C.

[0477] The specific steps are as follows:

[0478] 1) Prepare saturated solutions of free crystalline form A samples in different solvent systems at corresponding temperatures; 2) Add equal masses of free crystalline form A and free crystalline form B samples to the saturated solution to form a suspension; 3) Stir magnetically at room temperature; 4) After stirring for 2 days, separate the solid and test XRPD. The results are shown in Table 24. Free crystalline form A was obtained in all experiments. The experiment shows that compared with free crystalline form B, free crystalline form A is a more thermodynamically stable crystalline form at room temperature and 50°C.

[0479] Table 24 Suspension competition test results between free crystal forms A / B

[0480]

[0481] Example 4

[0482] Phosphate Form A

[0483] 300 mg of the compound shown in Formula I and 73.5 mg of phosphoric acid were slurried in 4 mL of IPA / H2O (19:1, v / v) solution at room temperature for 2 days to obtain phosphate crystal form A. The XRPD of the phosphate crystal form A sample is as follows: Figure 7 The XRPD data are shown in Table 25 below. The TGA / DSC results are shown in Figure 8 and Fig. 9The TGA results showed that the sample had a 4.40% weight loss when heated to 150°C; the DSC results showed that the sample had two endothermic peaks at 103.6°C and 174.5°C (peak temperature). 1 The H NMR results are shown below. The results show that the molar ratio of IPA to the compound of formula I in the sample is 0.04 (-0.4 wt%). The HPLC / IC results show that the molar ratio of phosphoric acid to the compound of formula I is 1:1.

[0484] The phosphate crystal form A was identified by VT-XRPD. The results showed that ( Fig.10 ): After purging phosphate crystal form A under N2 conditions for 20 minutes, the crystal form remained unchanged; heated to 150°C under nitrogen protection, cooled to 30°C, and then exposed to air, it was observed to be converted into free crystal form B. Combined with TGA / DSC and 1 H NMR results show that phosphate crystal form A is a hydrate, which dehydrates under heating conditions to anhydrous phosphate crystal form B. The XRPD pattern of phosphate crystal form B is as follows: Fig.11 The XRPD data are shown in Table 26 below.

[0485] 1 H NMR (400MHz, DMSO-d6): δ8.67(1H,t),8.43(1H,d),7.71(1H,dd),7.41~7.15(7H,m),6.93(1H,d),6.8 7(1H,dd),4.31(2H,d),4.12(2H,t),3.72~3.66(4H,m),3.44(2H,m),2.86~2.75(6H,m),2.23(3H,s).

[0486] Table 25 XRPD diffraction peak data of phosphate crystal form A

[0487]

[0488]

[0489] Table 26 XRPD diffraction peak data of phosphate crystal form B

[0490]

[0491]

[0492] Fumarate Form A

[0493] 300 mg of the compound shown in Formula I and 73.5 mg of fumaric acid were slurried in 6 mL of MTBE solution at room temperature for 2 days to obtain fumarate salt form A. The XRPD of the fumarate salt form A sample is as follows: Fig.12 TGA / DSC results are shown in Fig.13 and Fig.14 The TGA results showed that the sample had a weight loss of 1.17% when heated to 150°C; the DSC results showed that the sample had an endothermic peak at 130.3°C, with an onset temperature of 128.2°C. 1 The H NMR results are shown below. The results show that the molar ratio of fumaric acid to the compound of formula I in the sample is 1:1, and the molar ratio of the residual solvent MTBE to the compound of formula I is 0.01 (-0.1 wt%).

[0494] The fumarate salt form A was studied by variable humidity XRPD (VH-XRPD). The results showed that ( Fig.15 ): After placing the fumarate crystal form A under 85% RH, a diffraction peak shift was observed; after the sample was placed back to 30% RH, the sample turned into fumarate crystal form A. Combined with the DVS test results of fumarate crystal form A (such as Fig.52 As shown in the figure, the fumarate sample gained weight significantly under high humidity (>70% RH), and it is speculated that the fumarate exists in a hydrate state under high humidity. Under low humidity conditions (such as 30% RH), the sample returns to the anhydrous fumarate crystal form A.

[0495] 1 H NMR (400MHz, DMSO-d6): δ8.67(1H,t),8.44(1H,d),7.71(1H,dd),7.41~7.15(7H,m),6.93(1H,s),6.87(1H,dd),6. 61(2H,s),4.32(2H,d),4.11(2H,t),3.73~3.68(4H,m),3.43(2H,m),2.83~2.73(6H,m),2.44(2H,d),2.23(3H,s).

[0496] Table 27 XRPD diffraction peak data of fumarate salt form A

[0497]

[0498]

[0499] p-Toluenesulfonate Form A

[0500] 300 mg of the compound of formula I and 121.5 mg of p-toluenesulfonic acid monohydrate were slurried in 6 mL of IPAc solution at room temperature for 2 days to obtain p-toluenesulfonate crystalline form A. The XRPD of the p-toluenesulfonate crystalline form A sample is as follows: Fig.16 TGA / DSC results are shown in Fig.17 and Fig.18The TGA results showed that the sample had a weight loss of 0.94% when heated to 150°C; the DSC results showed that the sample had an endothermic peak at 152.1°C, with an initial temperature of 149.9°C. 1 The H NMR results are as follows: The results show that the molar ratio of p-toluenesulfonic acid to the compound represented by Formula I in the sample is 1:1, and the molar ratio of the residual solvent IPAc to the compound represented by Formula I is 0.01 (-0.1 wt%).

[0501] 1 H NMR (400MHz, DMSO-d6): δ9.79(1H,s),8.69(1H,t),8.44(1H,d),7.73(1H,dd),7.47(2H,d),7.43

[0502] (1H,d),7.35~7.21(6H,m),7.12(2H,d),7.01~6.94(2H,m),4.36~4.29(4H,m) ,3.93(1H,s),3.81~3.45(8H,m),3.13~2.80(3H,m),2.29(3H,s),2.26(3H,s).

[0503] Table 28 XRPD diffraction peak data of p-toluenesulfonate crystal form A

[0504] Position.[°2θ] Relative strength.[%] Position.[°2θ] Relative strength.[%] 5.4061 50.32 19.9778 61.40 7.7375 20.44 21.0061 12.71 8.1037 40.15 21.8329 62.62 10.8067 22.25 22.8534 30.96 13.1118 2.94 23.4116 26.46 14.7415 61.45 24.3701 39.55 15.2264 7.77 26.1763 17.86 16.2076 5.59 27.2507 6.34 17.1253 54.33 28.5791 19.45 18.1038 100.00 30.4321 3.98 18.3589 38.45 31.2458 6.35 18.8288 80.63

[0505] Benzenesulfonate Form A

[0506] 300 mg of the compound shown in Formula I and 100.5 mg of benzenesulfonic acid were slurried in 6 mL of IPAc solution at room temperature for 2 days to obtain benzenesulfonate crystalline form A. The XRPD pattern of the benzenesulfonate crystalline form A sample is as follows: Fig.19 TGA / DSC results are shown in Fig. 20 and Fig.21 The TGA results showed that the sample had a weight loss of 1.28% when heated to 140°C; the DSC results showed that the sample had an endothermic peak at 146.4°C, with an onset temperature of 144.5°C. 1 H NMR was measured in DMSO-d6, and the results were as follows: The results showed that the molar ratio of benzenesulfonic acid to the compound of formula I in the sample was 1:1, and the molar ratio of the residual solvent IPAc to the compound of formula I was 0.01 (-0.1 wt%).

[0507] 1H NMR (400MHz, DMSO-d6): δ9.79(1H,s),8.68(1H,t),8.44(1H,d),7.73(1H,dd),7.61~7.58(2H,m),7.43(1H,d),7. 35~7.21(9H,m),7.01~6.94(2H,m),4.32(4H,m),3.93(1H,s),3.80~3.46(8H,m),3.13~2.81(3H,m),2.25(3H,s).

[0508] Table 29 XRPD diffraction peak data of benzenesulfonate salt form A

[0509] Position [°2θ] Relative strength [%] Position [°2θ] Relative strength [%] 4.2927 90.89 20.2214 43.49 5.7545 6.24 20.5266 100.00 8.4936 76.94 20.9947 73.78 10.0153 39.96 21.2345 28.85 10.6755 22.03 21.4984 24.65 11.1754 8.55 21.9486 45.89 11.4806 9.68 22.3819 23.59 12.7029 7.82 22.6234 14.90 13.8134 41.83 23.4571 10.81 14.4981 11.11 23.8950 42.58 15.2579 54.96 25.5219 30.50 16.8048 46.57 25.7195 28.44 16.9835 26.02 27.6008 3.86 17.8361 20.18 28.7734 9.90 18.4629 22.00 29.2011 12.35 18.7971 56.58 30.3950 5.38 19.1714 26.12 31.7722 4.14 19.7264 74.71 33.1659 6.58

[0510] Oxalate Form B

[0511] 300 mg of the compound of formula I and 79.5 mg of oxalic acid dihydrate were slurried in 12 mL of Acetone / n-heptane (1:1, v / v) solution at room temperature for 7 days, and then slurried at 55°C for 1 day to obtain oxalate crystal form B. The XRPD pattern of the oxalate crystal form B sample is shown in Fig. 22 TGA / DSC results are shown in Fig.23 and Fig.24 The TGA results showed that the sample had a weight loss of 1.21% when heated to 150°C; the DSC results showed that the sample had two endothermic peaks at 158.2°C and 218.7°C (peak temperature). 1 The H NMR results are as follows, showing that the molar ratio of the residual solvent Acetone to the compound of Formula I is 0.01 (-0.1 wt%). The HPLC / IC results show that the molar ratio of oxalic acid to the compound of Formula I is 1:1.

[0512] 1 H NMR (400MHz, DMSO-d6): δ8.68(1H,t),8.44(1H,d),7.72(1H,dd),7.41(1H,d),7.35~7.19(6H, m), 6.98~6.91(2H,m), 4.32~4.25(4H,m), 3.74~3.34(10H,m), 2.94~2.85(4H,m), 2.25(3H,s).

[0513] Table 30 XRPD diffraction peak data of oxalate crystal form B

[0514] Position [°2θ] Relative strength [%] Position [°2θ] Relative strength [%] 7.6303 39.67 20.8286 39.95 8.3152 56.34 21.2807 28.72 12.4726 31.39 22.0493 70.88 15.2505 70.07 23.8443 93.78 16.2944 100.00 24.5635 18.67 17.6634 71.80 25.0476 23.37 18.2646 82.23 26.4010 16.45 18.4892 59.67 27.4132 20.10 18.7712 90.80 28.3635 5.97 19.1571 67.01 29.2511 13.78 19.9191 16.34

[0515] Maleate salt form A

[0516] The compound of formula I (828906-01-A) and an equimolar amount of maleic acid were slurried in an acetone / n-heptane (1:1, v / v) solution for 3 days, and the solid sample was separated and vacuum dried to obtain maleate crystal form A. The XRPD and TGA / DSC results of the maleate crystal form A sample are listed in Figure 25-27 The TGA results showed that the sample had a 2.56% weight loss when heated to 120°C, and the DSC results showed that the sample had three endothermic peaks at 54.7°C, 125.2°C and 200.7°C (peak temperature). 1 The H NMR results are shown below. In the maleate salt form A, the molar ratio of maleic acid to the compound of formula I is 1.0, the molar ratio of residual solvent acetone to the compound of formula I is 0.03 (-0.3 wt%), and no residual n-heptane is observed.

[0517] 1 H NMR (400MHz, DMSO-d6): δ8.67(1H,t),8.44(1H,d),7.71(1H,dd),7.41~7.20(7H,m),6.99~ 6.93(2H,m),6.04(2H,s),4.33~4.28(4H,m),3.73(3H,s),2.98~2.80(3H,m),2.25(3H,s).

[0518] Table 31 XRPD diffraction peak data of maleate salt form A

[0519]

[0520]

[0521] Malate Form A

[0522] The compound of formula I and an equimolar amount of malic acid were slurried in an acetone / n-heptane (1:1, v / v) solution for 6 days, and the solid sample was separated and vacuum dried to obtain malate crystal form A. The sample was subjected to powder diffraction, TGA, and DSC experiments, and the obtained XRPD was as follows: Fig.28 The TGA / DSC results are shown in Fig.29 and Fig.30 The TGA results showed that the sample had a weight loss of 2.26% when heated to 150°C. The DSC results showed that the sample had three endothermic peaks at 44.6°C, 96.3°C and 215.8°C (peak temperature). 1The H NMR results are shown below. In the malate crystal form A sample, the molar ratio of malic acid to the compound represented by formula I is 1:1, the molar ratio of residual solvent acetone to the compound represented by formula I is 0.01 (-0.1 wt%), and the molar ratio of n-heptane to the compound represented by formula I is 0.02 (-0.3 wt%).

[0523] 1 H NMR (400MHz, CD3OD): δ8.40(1H,d),7.74(1H,dd),7.47(1H,d),7.31~7.29(4H,m),7.27~7.22(1H,m),7.19(1H,d),6.97(1H,d),6.93(1H,dd),4 .42(2H,s),4.34~4.31(3H,m),3.81(3H,t),3.67~3.62(4H,m),3.44(2H ,t),3.09(2H,s),2.91(2H,dd),2.77(1H,dd),2.53(1H,q),2.26(3H,s).

[0524] Table 32 XRPD diffraction peak data of malate crystal form A

[0525] Position [°2θ] Relative strength [%] Position [°2θ] Relative strength [%] 6.6262 7.38 19.7373 21.21 8.9534 20.94 21.6214 25.16 9.8936 38.20 23.1988 17.64 13.2054 50.38 23.8001 22.22 16.1763 29.75 24.7654 32.77 16.5259 50.45 27.2491 13.36 17.8951 33.19 31.4661 5.26 18.9290 100.00

[0526] Succinate Form A

[0527] The succinate salt form A is obtained by slurrying the compound shown in formula I and an equal molar amount of succinic acid in MTBE solution for 6 days, separating the solid sample and vacuum drying. The XRPD and TGA / DSC results of the succinate salt form A are listed in Figure 31-33 The TGA results showed that the sample had a weight loss of 4.49% when heated to 150°C. The DSC results showed that the sample had two endothermic peaks at 57.3°C and 85.4°C (peak temperature). 1 The HNMR results show that in the succinate salt form A, the molar ratio of succinic acid to the compound represented by formula I is 1.2:1, and no residual MTBE solvent is observed.

[0528] 1H NMR (400MHz, CD3OD): δ8.40(1H,d),7.74(1H,dd),7.47(1H,d),7.32~7.31( 4H,m),7.27~7.22(1H,m),7.16(1H,d),6.95(1H,d),6.91(1H,dd),4.43(2H ,s),4.25(2H,t),3.83(2H,d),3.76(2H,dd),3.69~3.65(2H,m),3.41~3.37 (2H,m),3.21(2H,t),3.00(2H,s),2.69(2H,dd),2.55(5H,s),2.26(3H,s).

[0529] Table 33 XRPD diffraction peak data of succinate salt form A

[0530] Position [°2θ] Relative strength [%] Position [°2θ] Relative strength [%] 6.9349 100.00 19.4760 19.47 9.1969 38.52 20.2096 35.96 11.7777 6.58 20.9648 45.17 13.8697 56.93 22.1780 31.28 14.6969 18.62 23.0453 19.19 16.2949 72.71 23.9225 28.52 17.3959 14.28 26.1847 32.80 17.9354 39.73 28.0540 5.21 18.3860 12.73 34.8694 3.06

[0531] Methanesulfonate Form A / B

[0532] Methanesulfonate crystal form A is obtained by slurrying the compound represented by formula I and methanesulfonic acid in an acetone / n-heptane (1:1, v / v) solution at a molar ratio of 1:1 for 3 days, separating the colloidal solid sample and vacuum drying; methanesulfonate crystal form B is obtained by slurrying the compound represented by formula I and methanesulfonic acid in an IPAc solution at a molar ratio of 1:2 for 3 days, separating the solid sample and vacuum drying. The XRPD patterns of the methanesulfonate crystal forms A and B are shown respectively. Fig.34 and Fig.35 shown.

[0533] The TGA / DSC results of mesylate form B are detailed in Fig.36 and Fig.37 The TGA results showed that the sample had a weight loss of 0.91% when heated to 80°C and a weight loss of 2.40% when heated from 80°C to 130°C; the DSC results showed that the sample had an endothermic peak at 109.4°C (peak temperature). 1 The H NMR results are as follows: in the mesylate salt form B, the molar ratio of methanesulfonic acid to the compound of formula I is 2.1, and the molar ratio of the residual solvent IPAc to the compound of formula I is 0.04 (-0.7 wt %).

[0534] Methanesulfonate Form B: 1H NMR (400MHz, CD3OD): δ8.80(1H,s),8.52(1H,d),8.01(1H,dd),7.36~7.33(5H,m),7.30~7.27(1H,m),7.09~7.01(2H,m),4.45(2H,s),4.41~4 .40(3H,m),4.17~4.15(2H,m),4.05(2H,t),3.90(2H,d),3.71(2H,s), 3.65~3.57(5H,m),3.16(2H,s),2.93(2H,t),2.69(6H,d),2.35(3H,s).

[0535] Table 34 XRPD diffraction peak data of mesylate crystal form A

[0536] Position.[°2θ] Relative strength.[%] Position.[°2θ] Relative strength.[%] 5.0258 56.54 20.5965 100.00 17.0335 38.98 23.3964 71.59 18.1100 61.40

[0537] Table 35 XRPD diffraction peak data of mesylate crystal form B

[0538] Position.[°2θ] Relative strength.[%] Position.[°2θ] Relative strength.[%] 9.8298 9.76 22.6933 23.52 11.3186 15.66 23.4414 73.53 11.8183 5.19 23.9398 15.74 12.6882 3.11 24.4552 60.92 13.7455 5.81 25.3114 10.00 14.3775 6.16 25.6224 15.39 15.4572 22.47 25.8897 14.19 16.5409 6.51 27.0121 4.85 16.9751 29.83 27.4334 6.22 17.2607 52.29 27.9938 6.98 17.6280 39.70 28.5662 8.75 18.4451 35.15 29.3314 8.75 18.8911 100.00 29.7831 9.39 19.6841 30.75 30.3249 5.40 20.4301 65.78 31.3892 5.83 21.0733 65.86 32.6597 5.59 21.5827 20.17 35.2268 6.84 22.0878 29.37 37.3650 3.62

[0539] Oxalate Form A

[0540] Oxalate Form A is obtained by slurrying the compound of Formula I and oxalic acid in an equal molar ratio in an IPA / H2O (19:1, v / v) solution for 3 days, separating the solid sample and vacuum drying it. The XRPD of Oxalate Form A is as follows Fig.38 shown.

[0541] The TGA / DSC results of oxalate form A are listed in Fig.39 and Fig.40 The TGA results showed that the sample had a weight loss of 4.10% when heated to 150°C. The DSC results showed that the sample had three endothermic peaks at 153.6°C, 162.8°C and 218.8°C (peak temperature). 1 The H NMR results are as follows: in the oxalate salt form A, the molar ratio of the residual solvent IPA to the compound of formula I is 0.03 (-0.3 wt %).

[0542] Oxalate Form A: 1 H NMR (400MHz, DMSO-d6): δ8.67(1H,t),8.44(1H,d),7.72(1H,dd),7.41(1H,d),7.35~7.18(6H, m), 6.98~6.91(2H,m), 4.33~4.26(4H,m), 3.74~3.35(10H,m), 2.94~2.85(4H,m), 2.25(3H,s).

[0543] Table 36 XRPD diffraction peak data of oxalate crystal form A

[0544]

[0545]

[0546] 2-Hydroxyethanesulfonate Form A

[0547] The 2-hydroxyethanesulfonate salt form A is prepared by slurrying the compound of formula I and an equimolar amount of 2-hydroxyethanesulfonic acid in an acetone / n-heptane (1:1, v / v) solution for 3 days, separating the solid sample and vacuum drying it. The XRPD of the 2-hydroxyethanesulfonate salt form A sample is as follows Fig.41 The TGA / DSC results are shown in Fig.42 and Fig.43 The TGA results showed that the sample had a weight loss of 1.28% when heated to 110°C. The DSC results showed that the sample had two endothermic peaks at 57.4°C and 118.4°C (peak temperature). 1 The H NMR results are shown below. In the 2-hydroxyethanesulfonate salt form A, the molar ratio of 2-hydroxyethanesulfonic acid to the compound represented by Formula I is 1.2, the molar ratio of the residual solvent acetone to the compound represented by Formula I is 0.03 (-0.3 wt%), and the molar ratio of n-heptane to the compound represented by Formula I is 0.01 (-0.2 wt%).

[0548] 1 H NMR (400MHz, DMSO-d6): δ9.78(1H,s),8.67(1H,t),8.44(1H,d),7.73(1H,dd),7.43~7.21(7H,m),7.00~6.9 4(2H,m),4.37~4.30(4H,m),3.93(1H,s),3.77~3.45(10H,m),3.13~2.80(3H,m),2.60(2H,t),2.25(3H,s).

[0549] Table 37 XRPD diffraction peak data of 2-hydroxyethanesulfonate crystal form A

[0550] Position.[°2θ] Relative strength.[%] Position.[°2θ] Relative strength.[%] 4.8473 97.56 20.3297 56.13 9.8479 49.33 21.8277 45.05 10.9792 82.75 22.3258 67.31 12.8290 12.79 22.8682 63.84 14.2549 4.53 24.9854 21.98 15.5419 25.71 26.2466 10.34 15.9356 30.48 26.9452 8.37 16.6623 12.53 28.5116 17.43 18.0907 88.25 31.1759 4.85 19.3520 100.00

[0551] Example 5 Performance Evaluation Experiment

[0552] Dynamic solubility experiment

[0553] The solid feed concentration of 10 mg / mL (based on the compound shown in Formula I) was rotated and mixed at 37°C, and the solubility of each sample in four systems of water, SGF, FaSSIF and FeSSIF was measured at different time points (1, 4 and 24 hours). After sampling at each time point, the samples were centrifuged (10000rpm) and filtered (0.45μm PTFE filter head), and the HPLC concentration and pH value of the filtrate were measured. The solid samples after centrifugation were tested by XRPD. The solubility test results are summarized in Table 38, and the solubility curves in each system are shown in Figures 44-47 Compared with the free form A, different salt samples showed different degrees of solubility improvement in H2O, SGF and FaSSIF, among which the solubility of fumarate form A and oxalate form B in H2O and FaSSIF was higher than that of other salt forms.

[0554] Preparation of biosolvents

[0555] Preparation of simulated gastric fluid (SGF)

[0556] Weigh 100 mg NaCl and 50 mg Trinaton X-100 into a 50 mL volumetric flask and add purified water to dissolve. Add 816 μL 1M hydrochloric acid and adjust the pH to 1.8 with 1M hydrochloric acid or 1M NaOH solution. Add purified water to make up to volume.

[0557] Preparation of fasting-simulated intestinal fluid (FaSSIF)

[0558] Weigh 340 mg of anhydrous NaH2PO4 and 620 mg of NaCl into a 100-mL volumetric flask. Add purified water to dissolve, then add 55.44 μL of 50% NaOH solution, and adjust the pH to 6.5 with 1M hydrochloric acid or 1M NaOH solution. Add purified water and make up to volume. Then weigh 110 mg of SIF powder into a 50-mL volumetric flask, dissolve with the above solution, and make up to volume.

[0559] Preparation of simulated fed intestinal fluid (FeSSIF)

[0560] Take 0.82mL of glacial acetic acid and 1.18g of NaCl to a 100-mL volumetric flask, add purified water to dissolve, then add 528μL of 50% NaOH solution, adjust the pH to 5.0 with 1M hydrochloric acid or 1M NaOH solution, add purified water to make up to volume. Then weigh 560mg of SIF powder to a 50mL volumetric flask, dissolve with the above solution, and make up to volume.

[0561] Table 38 Summary of 37℃ dynamic solubility test results

[0562]

[0563]

[0564] S: solubility (mg / mL); --: XRPD not tested.

[0565] Hygroscopicity test

[0566] The hygroscopicity of phosphate form A, fumarate form A, p-toluenesulfonate form A, benzenesulfonate form A, oxalate form B and free form A was evaluated by dynamic moisture sorption (DVS). The mass change percentage of the samples was collected under constant temperature of 25°C and with humidity changes (0%RH-95%RH). The DVS test results and the XRPD results of the samples before and after the DVS test are shown in Figure 2. Figure 48-Figure 59 As shown. The results show that the free form A is almost non-hygroscopic, while the toluenesulfonate form A, benzenesulfonate form A and oxalate form B are slightly hygroscopic. Phosphate form A is a hydrate and dehydrates rapidly below 10% RH. Fumarate form A absorbs moisture significantly above 70% RH. All of the above forms did not change in form after the DVS test, indicating that they have high stability in a high humidity environment.

[0567] Solid state stability

[0568] Phosphate Form A, fumarate Form A, p-toluenesulfonate Form A, benzenesulfonate Form A, oxalate Form B and free Form A were left unopened for 1 week at 25°C / 60%RH and 40°C / 75%RH, respectively, and then tested for physical and chemical stability by XRPD and HPLC. The purity data are listed in Table 39, and the XRPD results are listed in Figure 60-65 The results showed that no obvious purity change was observed in the free form A and different salt forms after being placed under 25°C / 60% RH and 40°C / 75% RH conditions for one week. The crystal forms of different samples remained unchanged after the stability test, indicating that all the above crystal forms have high solid-state stability.

[0569] Table 39 Summary of solid state stability evaluation

[0570]

[0571] The control compound (trade name Tirbanibulin) in the test example of the present invention is a dual-acting Src kinase and tubulin polymerization inhibitor, which has been approved by the FDA and the EU for topical treatment of facial or scalp actinic keratosis. The preparation of the control compound refers to patent WO2008 / 002676A2, and the structure of the control compound is as follows:

[0572]

[0573] Test Example 1: Inhibition of Tubulin Monomer Polymerization Test

[0574] Tubulin Polymerization Assay Kit (cytoskeleton, Cat. #BK011P) was used to carry out the compound inhibition of tubulin monomer polymerization experiment.

[0575] Before the test, place the 96-well plate (Corning Costar, Cat.#3686) that comes with the kit in an ELISA reader (MD, SpectraMax M5) and heat it to 37°C for 10 minutes. Take out the 96-well plate, add 5 μL of 12.5 μM compound solution or blank solution, and then put the 96-well plate into the ELISA reader and incubate it at 37°C for 1 minute to warm the compound solution to 37°C. Take out the 96-well plate and quickly add 50 μL of the reaction mixture prepared according to the supplier's instructions to each well. Complete the addition within 1 minute and avoid bubbles. Then immediately put the 96-well plate into the ELISA reader, shake it for 5 seconds, and use Kinetic mode with an excitation light of 360 nm and an emission light of 420 nm. Continuously detect at 37°C for 30 minutes to 60 minutes, every 30 seconds, and use the detection time as the X-axis and the fluorescence signal value as the Y-axis to obtain the tubulin monomer polymerization curve. Fig.66 As shown in Table 40, the larger the Vmax value of the polymerization curve and the higher the maximum fluorescence signal value, the lower the inhibition efficiency of the compound.

[0576] Table 40

[0577] Compound Blank control Control Compound Compounds shown in formula I Maximum signal value 739 611 478

[0578] The results of the compound inhibition test on tubulin polymerization are as follows Fig.66 As shown in Table 40, the results show that the Vmax value and the maximum fluorescence signal value of the polymerization curve corresponding to the compound represented by Formula I of the present invention are significantly smaller, indicating that it can significantly inhibit the polymerization of microtubule protein monomers, and compared with the control compound, the inhibitory activity is better.

[0579] Test Example 2: Compound inhibition of cell proliferation test

[0580] The proliferation assay of human skin squamous cell carcinoma cell A-431 (ATCC, CRL-1555) and actinic keratosis patient-derived cell HT 297.T (ATCC, CRL-7782) was used to detect the inhibitory effect of small molecule compounds on cell proliferation.

[0581] A-431 cells and HT 297.T cells were cultured in DMEM medium containing 10% fetal bovine serum and grown in a 37°C, 5% CO2 incubator. Logarithmic phase cells were seeded into 96-well cell culture plates at 1000 cells / well, 100 μL per well, and cultured overnight in a 37°C, 5% CO2 incubator. On the second day, 100 μL of a gradient diluted 2× test compound solution was added to each well, DMSO was used as a positive control, and 10 μM staurosporine (Aladdin, S102392) was set as a negative control group. The culture plates with added compounds were incubated in a 37°C, 5% CO2 incubator for 4 days. After incubation, the plates were used. luciferase assay system (Promega, G9243) was used to measure the fluorescence signal value on Envision 2104 Multilabel Reader according to the instructions provided by the supplier. The inhibition rate was calculated by the following formula, and then a curve was drawn with the Log value of the inhibitor concentration as the X-axis and the inhibition rate as the Y-axis. The IC was calculated using Graphpad 8.0 50 .

[0582] Inhibition% = (positive control group signal - test well signal) / (positive control group signal - negative control group signal) * 100

[0583] Table 41 Inhibition results of test compounds on proliferation of A-431 and HT 297 T cells

[0584] Test compound <![CDATA[A-431IC 50 (nM)]]> <![CDATA[HT 297.T IC 50 (nM)]]> Control compound 40.30 85.38 Compounds shown in formula I 22.60 41.31

[0585] The results of the cell proliferation inhibition test of the compounds are shown in Table 41. The results show that the compound of formula I in the present invention can significantly inhibit cell proliferation, especially the inhibitory effect on HT 297.T cells derived from human actinic keratosis patients is significantly better than that of the control compound, indicating that the compound of formula I in the present invention has a better therapeutic effect on actinic keratosis.

[0586] Test Example 3: Thermodynamic Solubility Test

[0587] Prepare phosphate buffered saline (PBS) at pH 7.4, FeSSIF solution at pH 6.5, and FaSSGF solution at pH 1.6. Accurately weigh the compound, add the prepared phosphate buffer at pH 7.4, FeSSIF solution at pH 6.5, and FaSSGF solution at pH 1.6, and prepare a solution with a concentration of 4 mg / mL, shake at 1000 rpm for 1 hour, and then incubate at room temperature overnight. The incubated solution was centrifuged at 12000 rpm for 10 minutes to remove undissolved particles, and the supernatant was transferred to a new centrifuge tube. After the supernatant was appropriately diluted, an acetonitrile solution containing an internal standard was added, and the standard curve prepared with the same matrix was used for quantification.

[0588] Table 42 Thermodynamic solubility test results

[0589]

[0590] The results of the thermodynamic solubility test are shown in Table 42. The results indicate that, compared with the control compound, the compound represented by Formula I of the present invention has a greater thermodynamic solubility under neutral conditions and has good drugability.

[0591] Test Example 4: Pharmacokinetic Test

[0592] For the pharmacokinetic test in mice, three male ICR mice, 20-25g, fasted overnight, were injected with drugs (1mg / kg or 5mg / kg) through the tail vein, and blood was collected before and 15, 30min, and 1, 2, 4, 8, and 24h after administration. Three other mice were given oral gavage (5mg / kg), and blood was collected before and 15, 30min, and 1, 2, 4, 8, and 24h after administration. The blood samples were centrifuged at 6800g, 2-8℃ for 6min, and the plasma was collected and stored at -80℃. The plasma at each time point was taken, mixed with 3-5 times the amount of acetonitrile solution containing the internal standard, vortexed for 1 minute, centrifuged at 4℃ for 10min at 13000 rpm, and the supernatant was mixed with 3 times the amount of water, and an appropriate amount of the mixed solution was taken for LC-MS / MS analysis. The main pharmacokinetic parameters were analyzed by non-compartmental model using WinNonlin 7.0 software.

[0593] Table 43 Mouse pharmacokinetic test results 1

[0594]

[0595]

[0596] Table 44 Mouse pharmacokinetic test results 3

[0597]

[0598] The results of the mouse pharmacokinetic test are shown in Table 43 and Table 44. The results show that compared with the control compound, the compound represented by Formula I of the present invention is rapidly metabolized in mice, has low potential systemic toxicity, and has good drugability.

[0599] Test Example 5: Human liver microsome stability test

[0600] The stability test of human liver microsomes was performed by incubating the compound with human liver microsomes in vitro. First, the compound to be tested was prepared into a 10mM stock solution in DMSO solvent, and then the compound was diluted to 0.5mM with acetonitrile. Human liver microsomes (Corning) were diluted with PBS to form a microsome / buffer solution, and the solution was used to dilute 0.5mM of the compound to form a working solution. The compound concentration in the working solution was 1.5μM and the human liver microsome concentration was 0.75mg / ml. Take a deep well plate, add 30μL of working solution to each well, and then add 15μL of preheated 6mNADPH solution to start the reaction and incubate at 37°C. At 0, 5, 15, 30, and 45 minutes of incubation, add 135μL of acetonitrile to the corresponding wells to terminate the reaction. After terminating the reaction with acetonitrile at the last 45 minutes, the deep well plate was vortexed for 10 minutes (600rpm / min) and then centrifuged for 15 minutes. After centrifugation, the supernatant was collected and purified water was added in a 1:1 ratio for LC-MS / MS detection. The ratio of the peak area of ​​the compound to the peak area of ​​the internal standard at each time point was obtained. The peak area ratio of the compound at 5, 15, 30, and 45 minutes was compared with the peak area ratio at 0 minute, and the remaining percentage of the compound at each time point was calculated. Graphpad 5 software was used to calculate T 1 / 2 .

[0601] Table 45 Human liver microsome stability test results

[0602] Compound No. T1 / 2(min) Control Compound 32.23 Compounds shown in formula I 17.24

[0603] The results of the human liver microsome stability test are shown in Table 45, which indicate that the compound represented by Formula I of the present invention is rapidly metabolized in human liver microsomes, has low potential systemic toxicity, and has good drugability.

[0604] Test Example 6: Compounds inhibit Src signaling pathway

[0605] The Western Blot method was used to detect the inhibition of p-SRC by the compounds on A-431 skin cancer cells (ATCC, CRL-1555) to evaluate the inhibitory effect of the compounds on the SRC signaling pathway.

[0606] A-431 cells were cultured in DMEM medium containing 10% fetal bovine serum and placed in a 37°C, 5% CO2 incubator for growth. 500,000 cells / well were inoculated in a 12-well cell culture plate and placed in a 37°C, 5% CO2 incubator for overnight culture. The culture medium was replaced on the second day, and different concentrations of compounds were added for treatment. DMSO was used as a control. The culture plate with the compound added was placed in a 37°C, 5% CO2 incubator for further culture for 24 hours. The cells were washed once with PBS, and the cells were lysed with RIPA lysis buffer (R0010, Solebo) at low temperature for 30 minutes. After that, the protein lysate was collected in a centrifuge tube, centrifuged at 14,000g for 10 minutes at 4°C, and the supernatant was transferred to a new tube. The BCA protein concentration assay kit (P0009, Bio-Tech) was used for detection and calculation of protein concentration. The protein quantification of each sample was consistent using 5× protein loading buffer, boiled at 100°C for 5 min, and the p-SRC level was detected by western blot. The p-SRC antibody (Ab185617) was purchased from Abcam, and the GAPDH antibody (60004-1-Ig) was purchased from Proteintech.

[0607] The test results are as follows Fig.67 As shown, the results show that the compound represented by formula I of the present invention can significantly inhibit the phosphorylation of SRC at 80 nM, and compared with the control compound, has better p-SRC inhibitory activity and can block the downstream signaling pathway of SRC.

[0608] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A crystalline form or salt form of a compound as shown in formula I, in, The crystalline form of the compound shown in Formula I is free crystalline form A or free crystalline form B, The free crystalline form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 14.49±0.2°, 17.02±0.2°, 18.42±0.2°, and 20.53±0.2°; The free crystalline form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 16.55±0.2°, 17.77±0.2°, 20.36±0.2°, 21.24±0.2°, and 22.66±0.2°; The salt form of the compound as shown in formula I is phosphate, fumarate, p-toluenesulfonate, benzenesulfonate, oxalate, maleate, malate, succinate, methanesulfonate or 2-hydroxyethanesulfonate.

2. The crystalline form or salt form of the compound of formula I according to claim 1, characterized in that: The phosphate of the compound as shown in Formula I is the phosphate crystal form A or the phosphate crystal form B of the compound as shown in Formula I; In the phosphate crystal form A, the X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles has diffraction peaks at 6.74±0.2°, 13.47±0.2°, 15.69±0.2°, 18.09±0.2°, and 20.26±0.2°; In the phosphate crystal form B, the X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles has diffraction peaks at 6.68±0.2°, 13.37±0.2°, 14.16±0.2°, 15.30±0.2°, 16.74±0.2°, and 20.12±0.2°; Or, the fumarate of the compound as shown in Formula I is the fumarate crystalline form A of the compound as shown in Formula I; In the fumarate salt form A, the X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles has diffraction peaks at 13.51±0.2°, 15.41±0.2°, 17.57±0.2°, 19.48±0.2°, and 20.11±0.2°; Or, the p-toluenesulfonate of the compound as shown in Formula I is the p-toluenesulfonate crystalline form A of the compound as shown in Formula I; In the p-toluenesulfonate crystalline form A, the X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles has diffraction peaks at 5.41±0.2°, 8.10±0.2°, 14.74±0.2°, 17.13±0.2°, 18.10±0.2°, and 19.98±0.2°; Or, the benzenesulfonate salt of the compound as shown in Formula I is the benzenesulfonate salt crystal form A of the compound as shown in Formula I; In the benzenesulfonate salt form A, the X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles has diffraction peaks at 4.29±0.2°, 8.49±0.2°, 10.02±0.2°, 13.81±0.2°, and 15.26±0.2°; Or, the oxalate of the compound as shown in Formula I is the oxalate crystal form B or the oxalate crystal form A of the compound as shown in Formula I; In the oxalate crystal form B, the X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles has diffraction peaks at 7.63±0.2°, 8.32±0.2°, 15.25±0.2°, 16.29±0.2°, 22.05±0.2°, and 23.84±0.2°; The oxalate crystal form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 7.32±0.2°, 8.47±0.2°, 14.62±0.2°, 17.00±0.2°, 18.58±0.2°, and 19.44±0.2°; Or, the maleate of the compound as shown in Formula I is the maleate crystalline form A of the compound as shown in Formula I; In the maleate salt form A, the X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles has diffraction peaks at 13.54±0.2°, 16.92±0.2°, 17.64±0.2°, 19.61±0.2°, and 23.77±0.2°; Or, the malate of the compound of formula I is malate crystalline form A of the compound of formula I; In the malate crystalline form A, the X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles has diffraction peaks at 8.95±0.2°, 9.89±0.2°, 13.21±0.2°, 16.53±0.2°, and 18.93±0.2°; Or, the succinate of the compound as shown in Formula I is the succinate crystal form A of the compound as shown in Formula I; The succinate crystal form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 6.94±0.2°, 9.20±0.2°, 13.87±0.2°, 16.29±0.2°, 17.94±0.2°, and 20.21±0.2°; Or, the mesylate of the compound as shown in Formula I is the mesylate crystalline form A or mesylate B of the compound as shown in Formula I; The mesylate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 5.03±0.2°, 17.03±0.2°, 18.11±0.2°, 20.60±0.2°, and 23.40±0.2°; The mesylate salt form B has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 18.89±0.2°, 20.43±0.2°, 21.07±0.2°, 23.44±0.2°, and 24.46±0.2°; Or, the 2-hydroxyethanesulfonate of the compound as shown in Formula I is the 2-hydroxyethanesulfonate crystalline form A of the compound as shown in Formula I; The 2-hydroxyethanesulfonate salt form A has an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 4.85±0.2°, 9.85±0.2°, 10.98±0.2°, 18.09±0.2°, 19.35±0.2°, and 20.33±0.2°.

3. The crystalline form or salt form of the compound as shown in formula I according to claim 2, characterized in that: The free crystalline form A has an X-ray powder diffraction pattern expressed in 2θ angles using Cu-Kα radiation that satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 7.25±0.2°, 9.20±0.2°, 12.39±0.2°, 13.77±0.2°; (2) It has diffraction peaks at 3.66±0.2°, 7.25±0.2°, 9.20±0.2°, 11.13±0.2°, 12.39±0.2°, 13.77±0.2°, and 14.49±0.2°; (3) It has diffraction peaks at 7.25±0.2°, 9.20±0.2°, 12.39±0.2°, 13.77±0.2°, 14.49±0.2°, 17.02±0.2°, 17.78±0.2°, 18.42±0.2°, and 20.53±0.2°; (4) It has diffraction peaks at 3.66±0.2°, 7.25±0.2°, 9.20±0.2°, 11.13±0.2°, 12.39±0.2°, 13.77±0.2°, 14.49±0.2°, 17.02±0.2°, 17.78±0.2°, 18.42±0.2°, and 20.53±0.2°; (5) It has diffraction peaks at 3.66±0.2°, 7.25±0.2°, 9.20±0.2°, 11.13±0.2°, 12.39±0.2°, 13.77±0.2°, 14.49±0.2°, 17.02±0.2°, 17.78±0.2°, 18.42±0.2°, 20.53±0.2°, and 20.92±0.2°; (6) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the X-ray powder diffraction pattern of the free crystalline form B using Cu-Kα radiation and expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 8.89±0.2°, 10.99±0.2°, 13.81±0.2°, 16.10±0.2°, 19.65±0.2°; (2) It has diffraction peaks at 8.89±0.2°, 10.99±0.2°, 13.81±0.2°, 16.10±0.2°, 16.55±0.2°, 17.77±0.2°, 19.65±0.2°, 20.36±0.2°, 21.24±0.2°, and 22.66±0.2°; (3) it has diffraction peaks at 8.89±0.2°, 10.99±0.2°, 13.81±0.2°, 14.97±0.2°, 16.10±0.2°, 16.55±0.2°, 17.77±0.2°, 19.65±0.2°, 20.36±0.2°, 21.24±0.2°, 22.66±0.2°, 23.92±0.2°, 24.80±0.2°, 25.41±0.2°, and 26.65±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the X-ray powder diffraction pattern of the phosphate crystal form A using Cu-Kα radiation and expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 11.87±0.2°, 12.56±0.2°, 13.75±0.2°, 18.60±0.2°, 20.26±0.2°, 25.26±0.2°; (2) It has diffraction peaks at 6.74±0.2°, 11.87±0.2°, 12.56±0.2°, 13.47±0.2°, 13.75±0.2°, 15.69±0.2°, 16.86±0.2°, 18.09±0.2°, and 20.26±0.2°; (3) it has diffraction peaks at 3.40±0.2°, 6.74±0.2°, 7.47±0.2°, 11.87±0.2°, 12.56±0.2°, 13.47±0.2°, 13.75±0.2°, 14.94±0.2°, 15.69±0.2°, 16.86±0.2°, 18.09±0.2°, 18.61±0.2°, 20.26±0.2°, and 25.26±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the X-ray powder diffraction pattern of the phosphate crystal form B using Cu-Kα radiation and expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 3.35±0.2°, 14.53±0.2°, 21.27±0.2°, 22.53±0.2°, 24.43±0.2°, 25.24±0.2°; (2) It has diffraction peaks at 6.68±0.2°, 13.37±0.2°, 14.16±0.2°, 14.53±0.2°, 15.30±0.2°, 16.74±0.2°, 20.12±0.2°, and 21.26±0.2°; (3) It has diffraction peaks at 3.35±0.2°, 6.68±0.2°, 13.37±0.2°, 14.16±0.2°, 14.53±0.2°, 15.30±0.2°, 16.74±0.2°, 20.12±0.2°, 21.26±0.2°, 22.53±0.2°, 24.42±0.2°, and 25.24±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the fumarate salt form A uses Cu-Kα radiation and the X-ray powder diffraction pattern expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 9.03±0.2°, 9.78±0.2°, 16.89±0.2°, 22.04±0.2°, 23.71±0.2°, 24.24±0.2°, 25.72±0.2°; (2) It has diffraction peaks at 9.03±0.2°, 9.78±0.2°, 13.51±0.2°, 15.41±0.2°, 16.89±0.2°, 17.57±0.2°, 19.48±0.2°, 20.11±0.2°, and 22.04±0.2°; (3) It has diffraction peaks at 9.03±0.2°, 9.78±0.2°, 13.51±0.2°, 15.41±0.2°, 16.89±0.2°, 17.57±0.2°, 19.48±0.2°, 20.11±0.2°, 22.04±0.2°, 23.71±0.2°, 24.24±0.2°, and 25.72±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the p-toluenesulfonate crystalline form A uses Cu-Kα radiation and the X-ray powder diffraction pattern expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 10.81±0.2°, 18.83±0.2°, 21.83±0.2°, 24.37±0.2°; (2) It has diffraction peaks at 5.41±0.2°, 7.74±0.2°, 8.10±0.2°, 10.81±0.2°, 14.74±0.2°, 17.13±0.2°, 18.10±0.2°, 18.83±0.2°, and 19.98±0.2°; (3) it has diffraction peaks at 5.41±0.2°, 7.74±0.2°, 8.10±0.2°, 10.81±0.2°, 14.74±0.2°, 17.13±0.2°, 18.10±0.2°, 18.83±0.2°, 19.98±0.2°, 21.01±0.2°, 21.83±0.2°, 22.85±0.2°, 23.41±0.2°, 24.37±0.2°, 26.18±0.2°, and 28.58±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the benzenesulfonate salt form A uses Cu-Kα radiation and the X-ray powder diffraction pattern expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 10.68±0.2°, 16.80±0.2°, 18.80±0.2°, 19.73±0.2°, 20.53±0.2°, 20.99±0.2°; (2) It has diffraction peaks at 4.29±0.2°, 8.49±0.2°, 10.02±0.2°, 10.68±0.2°, 13.81±0.2°, 15.26±0.2°, 16.80±0.2°, 18.80±0.2°, 19.73±0.2°, 20.53±0.2°, and 20.99±0.2°; (3) it has diffraction peaks at 4.29±0.2°, 5.75±0.2°, 8.49±0.2°, 10.02±0.2°, 10.68±0.2°, 11.18±0.2°, 11.48±0.2°, 12.70±0.2°, 13.81±0.2°, 15.26±0.2°, 16.80±0.2°, 18.80±0.2°, 19.73±0.2°, 20.53±0.2°, 20.99±0.2°, 21.95±0.2°, and 23.90±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the X-ray powder diffraction pattern of the oxalate crystal form B using Cu-Kα radiation and expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 12.47±0.2°, 17.66±0.2°, 18.26±0.2°, 18.77±0.2°, 19.16±0.2°; (2) It has diffraction peaks at 7.63±0.2°, 8.32±0.2°, 12.47±0.2°, 15.25±0.2°, 16.29±0.2°, 17.66±0.2°, 18.26±0.2°, 18.77±0.2°, 19.16±0.2°, 22.05±0.2°, and 23.84±0.2°; (3) it has diffraction peaks at 7.63±0.2°, 8.32±0.2°, 12.47±0.2°, 15.25±0.2°, 16.29±0.2°, 17.66±0.2°, 18.26±0.2°, 18.77±0.2°, 19.16±0.2°, 19.92±0.2°, 20.83±0.2°, 21.28±0.2°, 22.05±0.2°, 23.84±0.2°, 25.05±0.2°, 26.40±0.2°, 27.41±0.2°, and 29.25±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the X-ray powder diffraction pattern of the oxalate crystal form A using Cu-Kα radiation and expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 12.93±0.2°, 13.47±0.2°, 15.23±0.2°, 22.38±0.2°, 26.00±0.2°; (2) It has diffraction peaks at 7.32±0.2°, 8.47±0.2°, 12.93±0.2°, 13.47±0.2°, 14.62±0.2°, 15.23±0.2°, 17.00±0.2°, 18.58±0.2°, 19.44±0.2°, 22.38±0.2°, and 26.00±0.2°; (3) it has diffraction peaks at 4.64±0.2°, 7.32±0.2°, 8.47±0.2°, 12.93±0.2°, 13.47±0.2°, 14.62±0.2°, 15.23±0.2°, 17.00±0.2°, 18.05±0.2°, 18.58±0.2°, 19.44±0.2°, 20.57±0.2°, 21.49±0.2°, 22.38±0.2°, 23.26±0.2°, 23.59±0.2°, and 26.00±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the maleate salt form A uses Cu-Kα radiation and the X-ray powder diffraction pattern expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 3.44±0.2°, 9.64±0.2°, 18.08±0.2°, 20.82±0.2°, 27.20±0.2°; (2) It has diffraction peaks at 3.44±0.2°, 9.64±0.2°, 13.54±0.2°, 16.92±0.2°, 17.64±0.2°, 18.08±0.2°, 19.61±0.2°, 20.82±0.2°, 23.77±0.2°, and 27.20±0.2°; (3) it has diffraction peaks at 3.44±0.2°, 9.64±0.2°, 13.54±0.2°, 16.92±0.2°, 17.64±0.2°, 18.08±0.2°, 19.61±0.2°, 20.82±0.2°, 22.36±0.2°, 22.71±0.2°, 23.77±0.2°, 27.20±0.2°, 28.90±0.2°, and 30.67±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the X-ray powder diffraction pattern of the malate crystalline form A using Cu-Kα radiation and expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at 8.95±0.2°, 9.89±0.2°, 13.21±0.2°, 16.17±0.2°, 16.53±0.2°, 18.93±0.2°, and 24.77±0.2°; (2) an X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles, with diffraction peaks at 6.63±0.2°, 8.95±0.2°, 9.89±0.2°, 13.21±0.2°, 16.17±0.2°, 16.53±0.2°, 18.93±0.2°, 21.62±0.2°, 23.20±0.2°, 23.80±0.2°, and 24.77±0.2°; (3) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the X-ray powder diffraction pattern of the succinate salt form A using Cu-Kα radiation and expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 14.70±0.2°, 17.40±0.2°, 19.48±0.2°, 20.96±0.2°, 22.18±0.2°, 23.04±0.2°, 23.92±0.2°, 26.18±0.2°; (2) It has diffraction peaks at 6.94±0.2°, 9.20±0.2°, 13.87±0.2°, 16.29±0.2°, 17.94±0.2°, 20.21±0.2°, 20.96±0.2°, 22.18±0.2°, and 26.18±0.2°; (3) it has diffraction peaks at 6.94±0.2°, 9.20±0.2°, 13.87±0.2°, 14.70±0.2°, 16.29±0.2°, 17.40±0.2°, 17.94±0.2°, 19.48±0.2°, 20.21±0.2°, 20.96±0.2°, 22.18±0.2°, 23.04±0.2°, 23.92±0.2°, and 26.18±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the mesylate salt form A uses Cu-Kα radiation and the X-ray powder diffraction pattern expressed in 2θ angles contains diffraction peak positions and relative intensities as shown in the following table: Or, the mesylate salt form B uses Cu-Kα radiation and the X-ray powder diffraction pattern expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 9.83±0.2°, 11.32±0.2°, 15.46±0.2°, 17.26±0.2°; (2) It has diffraction peaks at 9.83±0.2°, 11.32±0.2°, 15.46±0.2°, 17.26±0.2°, 18.89±0.2°, 20.43±0.2°, 21.07±0.2°, 23.44±0.2°, and 24.46±0.2°; (3) it has diffraction peaks at 9.83±0.2°, 11.32±0.2°, 15.46±0.2°, 16.98±0.2°, 17.26±0.2°, 17.63±0.2°, 18.89±0.2°, 19.68±0.2°, 20.43±0.2°, 21.07±0.2°, 21.58±0.2°, 22.09±0.2°, 22.69±0.2°, 23.44±0.2°, and 24.46±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table: Or, the X-ray powder diffraction pattern of the 2-hydroxyethanesulfonate salt form A using Cu-Kα radiation and expressed in 2θ angles satisfies any one of the following conditions: (1) It has diffraction peaks at one or more of the following locations: 15.54±0.2°, 15.94±0.2°, 21.83±0.2°, 22.33±0.2°, 22.87±0.2°; (2) It has diffraction peaks at 4.85±0.2°, 9.85±0.2°, 10.98±0.2°, 15.54±0.2°, 15.94±0.2°, 18.09±0.2°, 19.35±0.2°, 20.33±0.2°, 21.83±0.2°, 22.33±0.2°, and 22.87±0.2°; (3) It has diffraction peaks at 4.85±0.2°, 9.85±0.2°, 10.98±0.2°, 12.83±0.2°, 15.54±0.2°, 15.94±0.2°, 16.66±0.2°, 18.09±0.2°, 19.35±0.2°, 20.33±0.2°, 21.83±0.2°, 22.33±0.2°, and 22.87±0.2°; (4) The diffraction peak positions and relative intensities thereof are shown in the following table:

4. The crystalline form or salt form of the compound of formula I according to claim 3, characterized in that: The free crystalline form A of the compound shown in formula I satisfies one or more of the following conditions: (1) It is anhydrous crystalline; (2) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG1 ; (3) Its differential scanning calorimetry analysis chart has an endothermic peak starting point at 94.7±3°C; (4) Its differential scanning calorimetry analysis chart has an endothermic peak at 96.6±3°C; (5) Its thermogravimetric analysis shows a weight loss of approximately 0.98% at 150°C; (6) Its differential scanning calorimetry analysis diagram is shown in FIG3 ; (7) Its thermogravimetric analysis diagram is shown in Figure 2; Or, the free crystalline form B satisfies one or more of the following conditions: (1) It is anhydrous crystalline; (2) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG4 ; (3) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 77.2±3°C; (4) Its differential scanning calorimetry analysis chart has an endothermic peak at 84.5±3°C; (5) Its differential scanning calorimetry analysis chart has an endothermic peak at 92.4±3°C; (6) Its thermogravimetric analysis shows a weight loss of approximately 0.48% at 150°C; (7) Its differential scanning calorimetry analysis diagram is shown in FIG6 ; (8) Its thermogravimetric analysis diagram is shown in Figure 5; Or, the phosphate crystal form A satisfies one or more of the following conditions: (1) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG7 ; (2) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 172.8±3°C; (3) Its differential scanning calorimetry analysis chart has an endothermic peak at 174.5±3°C; (4) Its thermogravimetric analysis shows a weight loss of approximately 4.40% at 150°C; (5) Its differential scanning calorimetry analysis diagram is shown in FIG9 ; (6) Its thermogravimetric analysis diagram is shown in FIG8 ; (7) In the phosphate crystal form A, the molar ratio of the compound represented by formula I to phosphoric acid is 1:1; or, the phosphate crystal form B satisfies one or more of the following conditions: (1) It is anhydrous crystal type; (2) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG11 ; (3) In the phosphate crystal form B, the molar ratio of the compound shown in formula I to phosphoric acid is 1:1; or, the fumarate crystal form A satisfies one or more of the following conditions: (1) It is anhydrous crystal type; (2) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG12 ; (3) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 128.2±3°C; (4) Its differential scanning calorimetry analysis chart has an endothermic peak at 130.3±3°C; (5) Its thermogravimetric analysis shows a weight loss of approximately 1.17% at 150°C; (6) Its differential scanning calorimetry analysis diagram is shown in FIG14 ; (7) Its thermogravimetric analysis diagram is shown in FIG13 ; (8) In the fumarate salt crystalline form A, the molar ratio of the compound represented by formula I to fumaric acid is 1:1; Or, the p-toluenesulfonate crystalline form A satisfies one or more of the following conditions: (1) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG16 ; (2) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 149.9±3°C; (3) Its differential scanning calorimetry analysis chart has an endothermic peak at 152.1±3°C; (4) Its thermogravimetric analysis shows a weight loss of approximately 0.94% at 150°C; (5) Its differential scanning calorimetry analysis diagram is shown in FIG18 ; (6) Its thermogravimetric analysis diagram is shown in FIG17 ; (7) In the p-toluenesulfonate salt form A, the molar ratio of the compound represented by formula I to p-toluenesulfonic acid is 1:1; or, the benzenesulfonate salt form A satisfies one or more of the following conditions: (1) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG19 ; (2) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 144.5±3°C; (3) Its differential scanning calorimetry analysis chart has an endothermic peak at 146.4±3°C; (4) Its thermogravimetric analysis shows a weight loss of approximately 1.28% at 140°C; (5) Its differential scanning calorimetry analysis diagram is shown in FIG21 ; (6) Its thermogravimetric analysis diagram is shown in FIG20 ; (7) In the benzenesulfonate salt form A, the molar ratio of the compound represented by formula I to benzenesulfonic acid is 1:1; Or, the oxalate crystal form B satisfies one or more of the following conditions: (1) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG22 ; (2) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 155.5±3°C; (3) Its differential scanning calorimetry analysis chart has an endothermic peak at 158.2±3°C; (4) Its differential scanning calorimetry analysis chart has an endothermic peak at 218.7±3°C; (5) Its thermogravimetric analysis shows a weight loss of approximately 1.21% at 150°C; (6) Its differential scanning calorimetry analysis diagram is shown in FIG24 ; (7) Its thermogravimetric analysis diagram is shown in FIG23 ; (8) In the oxalate salt form B, the molar ratio of the compound represented by formula I to oxalic acid is 1:1; Or, the oxalate crystal form A satisfies one or more of the following conditions: (1) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG38 ; (2) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 151.3±3°C; (3) Its differential scanning calorimetry analysis chart has an endothermic peak at 153.6±3°C; (4) Its differential scanning calorimetry analysis chart has an endothermic peak at 162.8±3°C; (5) Its differential scanning calorimetry analysis chart has an endothermic peak at 218.8±3°C; (6) Its thermogravimetric analysis shows a weight loss of approximately 4.10% at 150°C; (7) Its differential scanning calorimetry analysis diagram is shown in FIG40 ; (8) Its thermogravimetric analysis diagram is shown in FIG39 ; Or, the maleate salt form A satisfies one or more of the following conditions: (1) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG25 ; (2) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 123.4±3°C; (3) Its differential scanning calorimetry analysis chart has an endothermic peak at 125.2±3°C; (4) Its thermogravimetric analysis shows a weight loss of approximately 2.56% at 120°C; (5) Its differential scanning calorimetry analysis diagram is shown in FIG27 ; (6) Its thermogravimetric analysis diagram is shown in FIG26 ; (7) In the maleate salt form A, the molar ratio of the compound of formula I to maleic acid is 1:1; Or, the malate crystal form A satisfies one or more of the following conditions: (1) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG28 ; (2) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 86.3±3°C; (3) Its differential scanning calorimetry analysis chart has an endothermic peak at 96.3±3°C; (4) Its thermogravimetric analysis shows a weight loss of approximately 2.26% at 150°C; (5) Its differential scanning calorimetry analysis diagram is shown in FIG30 ; (6) Its thermogravimetric analysis diagram is shown in FIG29 ; (7) In the malate crystalline form A, the molar ratio of the compound represented by formula I to malic acid is 1:1; Or, the succinate salt form A satisfies one or more of the following conditions: (1) In the succinate salt form A, the molar ratio of the compound of formula I to succinic acid is 1:1.2, 1:1.1 or 1:1; (2) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG31 ; (3) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 75.9±3°C; (4) Its differential scanning calorimetry analysis chart has an endothermic peak at 85.4±3°C; (5) Its thermogravimetric analysis shows a weight loss of approximately 4.49% at 150°C; (6) Its differential scanning calorimetry analysis diagram is shown in FIG33 ; (7) Its thermogravimetric analysis diagram is shown in FIG32 ; (8) In the succinate salt crystal form A, the molar ratio of the compound represented by formula I to succinic acid is 1:1; Or, the mesylate salt crystal form A uses Cu-Kα radiation and the X-ray powder diffraction pattern expressed in 2θ angle is shown in Figure 34; or, the mesylate salt crystal form B satisfies one or more of the following conditions: (1) In the mesylate salt form B, the molar ratio of the compound of formula I to methanesulfonic acid is 1:2.1 or 1:2; (2) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG35 ; (3) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 97.3±3°C; (4) Its differential scanning calorimetry analysis chart has an endothermic peak at 109.4±3°C; (5) Its thermogravimetric analysis shows a weight loss of about 0.91% at 80°C and a weight loss of about 2.40% at 80-130°C; (6) Its differential scanning calorimetry analysis diagram is shown in FIG37 ; (7) Its thermogravimetric analysis diagram is shown in FIG36 ; (8) In the mesylate salt form B, the molar ratio of the compound represented by formula I to methanesulfonic acid is 1:2; Or, the 2-hydroxyethanesulfonate salt form A satisfies one or more of the following conditions: (1) Its X-ray powder diffraction pattern using Cu-Kα radiation and expressed in 2θ angles is shown in FIG41 ; (2) Its differential scanning calorimetry analysis chart shows an endothermic peak starting point at 109.5±3°C; (3) Its differential scanning calorimetry analysis chart has an endothermic peak at 118.4±3°C; (4) Its thermogravimetric analysis shows a weight loss of approximately 1.28% at 110°C; (5) Its differential scanning calorimetry analysis diagram is shown in FIG43 ; (6) Its thermogravimetric analysis diagram is shown in FIG42 ; (7) In the 2-hydroxyethanesulfonate salt form A, the molar ratio of the compound represented by formula I to 2-hydroxyethanesulfonic acid is 1:

1.

5. A method for preparing a crystalline form or salt form of a compound as shown in formula I, characterized in that: The crystalline form of the compound shown in Formula I is the free crystalline form A or the free crystalline form B as described in any one of claims 1 to 4; The salt form of the compound of formula I is the phosphate crystal form A, phosphate crystal form B, fumarate crystal form A, p-toluenesulfonate crystal form A, benzenesulfonate crystal form A, oxalate crystal form B, oxalate crystal form A, maleate crystal form A, malate crystal form A, succinate crystal form A, methanesulfonate crystal form A, methanesulfonate crystal form B, or 2-hydroxyethanesulfonate crystal form A of the compound of formula I as claimed in any one of claims 2 to 4; in, The preparation method of the free-state crystalline form A comprises the following steps: dissolving the compound represented by formula I in a solvent, volatilizing at room temperature, and obtaining the free-state crystalline form A; the solvent is an organic solvent or a mixed solvent, and the organic solvent is preferably CHCl3, THF, acetone, toluene, cyclopentyl methyl ether, 2-methyltetrahydrofuran, isopropanol, IPAc or 2-butanone; the mixed solvent is a mixed solvent of an organic solvent and water, and the mixed solvent is preferably a mixed solvent of MeOH and H2O, or a mixed solvent of acetonitrile and H2O; The preparation method of the free-state crystal form B comprises the following steps: concentrating the compound solution as shown in formula I under reduced pressure, and drying at 40-60° C. to obtain the free-state crystal form B; the solution is an alcohol solution or a halogenated hydrocarbon solution; The preparation method of the phosphate crystal form A comprises the following steps: mixing the compound represented by formula I, phosphoric acid and a solvent, and slurrying at room temperature to obtain the phosphate crystal form A of the compound represented by formula I; the solvent is an ester solvent, an ether solvent, a mixed solvent of an alcohol solvent and water, or a mixed solvent of a ketone solvent and a saturated alkane solvent; The preparation method of the phosphate crystal form B comprises the following steps: heating the phosphate crystal form A to 150±10° C. to obtain the phosphate crystal form B; The preparation method of the fumarate salt crystal form A comprises the following steps: mixing the compound represented by formula I, fumaric acid and a solvent, and slurrying at room temperature to obtain the fumarate salt crystal form A; the solvent is an ester solvent, an ether solvent, a mixed solvent of an alcohol solvent and water, or a mixed solvent of a ketone solvent and a saturated alkane solvent; The preparation method of the p-toluenesulfonate crystalline form A comprises the following steps: mixing the compound represented by formula I, p-toluenesulfonic acid and a solvent, and slurrying at room temperature to obtain the p-toluenesulfonate crystalline form A; the solvent is an ester solvent or an ether solvent; The preparation method of the benzenesulfonate salt crystal form A comprises the following steps: mixing the compound represented by formula I, benzenesulfonic acid and a solvent, and beating at room temperature to obtain the benzenesulfonate salt crystal form A; the solvent is a mixed solvent of an ester solvent, an alcohol solvent and water; The preparation method of the oxalate crystal form B comprises the following steps: mixing the compound represented by formula I, oxalic acid and a solvent, and slurrying at room temperature to obtain the oxalate crystal form B; the solvent is a mixed solvent of an ester solvent, an ether solvent, a ketone solvent and a saturated alkane solvent; The preparation method of the oxalate crystal form A comprises the following steps: mixing the compound represented by formula I, oxalic acid and a solvent, and slurrying at room temperature to obtain the oxalate crystal form A; the solvent is a mixed solvent of an alcohol solvent and water; The preparation method of the maleate salt crystal form A comprises the following steps: mixing the compound represented by formula I, maleic acid and a solvent, and slurrying at room temperature to obtain the maleate salt crystal form A; the solvent is a mixed solvent of an ester solvent, an ether solvent, a ketone solvent and a saturated alkane solvent; The preparation method of the malate crystal form A comprises the following steps: mixing the compound represented by formula I, malic acid and a solvent, and slurrying at room temperature to obtain the malate crystal form A; the solvent is a mixed solvent of a ketone solvent and a saturated alkane solvent; The preparation method of the succinate salt crystal form A comprises the following steps: mixing the compound shown in formula I, succinic acid and a solvent, and slurrying at room temperature to obtain the succinate salt crystal form A; the solvent is an ether solvent; The preparation method of the mesylate salt crystal form A comprises the following steps: mixing the compound shown in formula I, methanesulfonic acid and a solvent, and beating at room temperature to obtain the mesylate salt crystal form A; the solvent is a mixed solvent of a ketone solvent and a saturated alkane solvent; The preparation method of the mesylate salt crystal form B comprises the following steps: mixing the compound shown in formula I, methanesulfonic acid and a solvent, and beating at room temperature to obtain the mesylate salt crystal form B; the solvent is a mixed solvent of an ester solvent, an ether solvent, a ketone solvent and a saturated alkane solvent; The preparation method of the 2-hydroxyethanesulfonate salt form A comprises the following steps: mixing the compound shown in formula I, 2-hydroxyethanesulfonic acid and a solvent, and slurrying at room temperature to obtain the 2-hydroxyethanesulfonate salt form A; the solvent is a mixed solvent of an ester solvent, a ketone solvent and a saturated alkane solvent.

6. The preparation method according to claim 5, characterized in that: In the preparation method of the free crystalline form B, the compound represented by formula I is dissolved in MeOH or dichloromethane and then rotary evaporated under reduced pressure, and the obtained colloidal sample is transferred to 50° C. and dried under vacuum to obtain; Or, in the method for preparing the phosphate crystal form A, the method for preparing the phosphate crystal form A satisfies one or more of the following conditions: (1) The molar ratio of the phosphoric acid to the compound of formula I is (1.0-1.7):1; preferably 1.2:1; (2) The molar volume ratio of the compound represented by Formula I to the solvent is 0.11-0.21 mol / L; preferably 0.16 mol / L; (3) In the mixed solvent of the alcohol solvent and water, the volume ratio of the alcohol solvent to the water is (14-24):1, preferably 19:1; (4) In the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1; (5) The solvent is a mixed solvent of IPA / H2O (19:1, v / v), a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether; Or, in the preparation method of the phosphate crystal form B, the preparation method of the phosphate crystal form B satisfies one or two of the following conditions: (1) the phosphate crystal form A is heated under nitrogen protection; (2) The heating temperature is 145-155° C., preferably 150° C.; Or, in the preparation method of the fumarate salt crystal form A, the preparation method of the fumarate salt crystal form A satisfies one or more of the following conditions: (1) The molar ratio of the fumaric acid to the compound of formula I is (1.0-1.5):1; preferably 1.0:1; (2) The molar volume ratio of the compound represented by Formula I to the solvent is 0.06-0.16 mol / L; preferably 0.11 mol / L; (3) In the mixed solvent of the alcohol solvent and water, the volume ratio of the alcohol solvent to the water is (14-24):1, preferably 19:1; (4) In the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1; (5) The solvent is a mixed solvent of IPA / H2O (19:1, v / v), a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether; Or, in the method for preparing the p-toluenesulfonate crystalline form A, the method for preparing the p-toluenesulfonate crystalline form A satisfies one or more of the following conditions: (1) The molar ratio of p-toluenesulfonic acid to the compound of formula I is (1.0-1.5):1; preferably 1.0:1; (2) The molar volume ratio of the compound represented by Formula I to the solvent is 0.06-0.16 mol / L; preferably 0.11 mol / L; (3) The solvent is isopropyl acetate or methyl tert-butyl ether; Or, in the preparation method of the benzenesulfonate salt form A, the preparation method of the benzenesulfonate salt form A satisfies one or more of the following conditions: (1) The molar ratio of the benzenesulfonic acid to the compound of formula I is (1.0-1.5):1; preferably 1.0:1; (2) The molar volume ratio of the compound represented by Formula I to the solvent is 0.06-0.16 mol / L; preferably 0.11 mol / L; (3) In the mixed solvent of the alcohol solvent and water, the volume ratio of the alcohol solvent to the water is (14-24):1, preferably 19:1; (4) The solvent is a mixed solvent of IPA / H2O (19:1, v / v) or isopropyl acetate; Or, in the preparation method of the oxalate crystal form B, the preparation method of the oxalate crystal form B satisfies one or more of the following conditions: (1) The molar ratio of the oxalic acid to the compound represented by Formula I is (1.0-1.5):1; preferably 1.0:1; (2) The molar volume ratio of the compound represented by Formula I to the solvent is 0.02-0.08 mol / L, preferably 0.05 mol / L; (3) In the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1; (4) The solvent is a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether; Or, in the method for preparing the oxalate crystal form A, the method for preparing the oxalate crystal form A satisfies one or more of the following conditions: (1) The molar ratio of the oxalic acid to the compound represented by Formula I is (1.0-1.5):1; preferably 1.0:1; (2) In the method for preparing the oxalate crystal form A, in the mixed solvent of the alcohol solvent and water, the volume ratio of the alcohol solvent to the water is (14-24):1, preferably 19:1; (3) In the preparation method of the oxalate salt form A, the solvent is a mixed solvent of IPA / H2O (19:1, v / v); Or, in the preparation method of the maleate salt crystalline form A, the preparation method of the maleate salt crystalline form A satisfies one or more of the following conditions: (1) The molar ratio of the maleic acid to the compound of formula I is (1.0-1.5):1; preferably 1.0:1; (2) In the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1; (3) The solvent is a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether; Or, in the method for preparing the malate crystalline form A, the method for preparing the malate crystalline form A satisfies one or more of the following conditions: (1) The molar ratio of malic acid to the compound of formula I is (1.0-1.5):1; preferably 1.0:1; (2) In the preparation method of the malate crystalline form A, in the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1, preferably 1:1; (3) The solvent is a mixed solvent of acetone / n-heptane (1:1, v / v); Or, in the preparation method of the succinate salt crystal form A, the preparation method of the succinate salt crystal form A satisfies one or two of the following conditions: (1) The molar ratio of succinic acid to the compound of formula I is (1.0-1.5):1; preferably 1.0:1; (2) The solvent is methyl tert-butyl ether; Or, in the method for preparing the mesylate salt form A, the method for preparing the mesylate salt form A satisfies one or more of the following conditions: (1) The molar ratio of the methanesulfonic acid to the compound of formula I is (1.0-1.2):1; preferably 1:1; (2) In the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1, preferably 1:1; (3) The solvent is a mixed solvent of acetone / n-heptane (1:1, v / v); Or, in the preparation method of the mesylate salt crystal form B, the preparation method of the mesylate salt crystal form B satisfies one or more of the following conditions: (1) The molar ratio of the methanesulfonic acid to the compound of formula I is (1.5-2.5):1; preferably 2:1; (2) In the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1; (3) The solvent is a mixed solvent of acetone / n-heptane (1:1, v / v), isopropyl acetate or methyl tert-butyl ether; Or, the preparation method of the 2-hydroxyethanesulfonate salt form A satisfies one or more of the following conditions: (1) The molar ratio of the 2-hydroxyethanesulfonic acid to the compound of formula I is (1.5-2.5):1; preferably 2:1; (2) In the mixed solvent of the ketone solvent and the saturated alkane solvent, the volume ratio of the ketone solvent to the saturated alkane solvent is (0.5-2):1; (3) The solvent is a mixed solvent of acetone / n-heptane (1:1, v / v) or isopropyl acetate.

7. A pharmaceutical composition, characterized in that It comprises a crystalline form or a salt form of the compound shown in formula I as described in any one of claims 1 to 6, and at least one pharmaceutical excipient.

8. A use of a substance M, characterized in that: The substance M is a crystalline form or salt form of a compound of formula I as described in any one of claims 1 to 6, or a pharmaceutical composition as described in claim 7, The uses include: 1) Inhibit tubulin polymerization and / or Src kinase; 2) Preventing and / or treating diseases related to tubulin polymerization and / or Src kinase; 3) Preparation of tubulin polymerization and / or Src kinase inhibitors; 4) Preparation of drugs or preparations for preventing and / or treating diseases related to tubulin polymerization and / or Src kinase.

9. Use of a substance M in preparing a drug for treating tumors and / or skin diseases, characterized in that: The substance M is a crystalline form or a salt form of the compound of formula I as described in any one of claims 1 to 6, or a pharmaceutical composition as described in claim 7.

10. The use according to claim 9, characterized in that The tumor includes: solid tumors, sarcomas, and hematological cancers; preferably, the tumor includes: breast cancer, ovarian cancer, prostate cancer, cervical cancer, testicular cancer, colon cancer, colorectal cancer, liver cancer, non-small cell lung cancer, squamous cell carcinoma (e.g., squamous cell carcinoma of the skin), small cell lung cancer, gastric cancer, gastrointestinal stromal tumors, pancreatic cancer, bladder cancer, germ cell tumors, mast cell tumors, mastocytosis, glioblastoma, neuroblastoma, astrocytoma, melanoma, B cell lymphoma, T cell lymphoma, slowly progressive lymphoma, Hodgkin's lymphoma, non-Hodgkin's lymphoma, acute myeloid leukemia, acute lymphocytic leukemia, chronic myeloid leukemia, chronic lymphocytic leukemia, myeloma and / or myelodysplastic syndrome; The skin diseases include actinic keratosis, psoriasis, atopic dermatitis, psoriasis, vitiligo, roseola and / or systemic lupus erythematosus.

Citation Information

Patent Citations

  • Biaryl compositions and methods for modulating a kinase cascade

    WO2008002676A2

Cited By

  • Salt form of complement factor b inhibitor, preparation method therefor, and use thereof

    WO2026158599A1